Water-based coating composition, cured coating film thereof, and coated article

The aqueous paint composition with balanced manganese-oxide catalyst, activated carbon, and water-based resins addresses the issue of weather resistance in ozone decomposition coatings by enhancing ozone degradation and preventing resin deterioration.

JP7625356B2Active Publication Date: 2025-02-03AISIN CHEM CO LTD +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2022018578
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-02-09
Publication Date
2025-02-03
Estimated Expiration
2042-02-09

AI Technical Summary

Technical Problem

Existing water-based paint compositions containing manganese-oxide-based catalysts and activated carbon for ozone decomposition suffer from weak weather resistance due to photocatalytic effects and ozone decomposition leading to resin deterioration, especially when exposed to light and air flow.

Method used

Aqueous paint compositions comprising manganese-oxide catalysts, activated carbon, and specific water-based resins with controlled glass transition temperatures and balanced ratios of manganese-oxide catalyst, activated carbon, and water-based resin to enhance weather resistance and ozone degradation performance.

Benefits of technology

The composition achieves high ozone degradation and resistance to deterioration under environmental conditions with light exposure, maintaining a stable and durable hardened coating film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007625356000005
    Figure 0007625356000005
  • Figure 0007625356000006
    Figure 0007625356000006
  • Figure 0007625356000007
    Figure 0007625356000007
Patent Text Reader

Abstract

To provide a water-based paint composition that includes a manganese oxide-based catalyst but yet forms a coating film with reduced chalking tendencies and improved weather resistance.SOLUTION: A water-based paint composition includes a manganese oxide-based catalyst, activated carbon, an aqueous resin, and a dispersant, with water being the chief ingredient of a solvent. The aqueous resin is one or more of acrylic resin, modified acrylic resin, and fluorocarbon resin.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an aqueous coating composition and a cured coating film thereof, as well as a coated article, which can be applied to, for example, vehicle structural parts, blowers, and other parts through which air flows, and which can purify the air by decomposing ozone in the air. In particular, the present invention relates to an aqueous coating composition and a cured coating film thereof, as well as a coated article, which can improve the weather resistance of the coating film. [Background technology]

[0002] Nitrogen oxides (NO X Volatile organic compounds (VOCs) such as benzene, non-methane organic gases (NMOG), and hydrocarbons (HC) react with oxygen in the atmosphere or undergo photochemical changes due to ultraviolet rays from sunlight to become photochemical oxidants (O x ). These photochemical oxidants are air pollutants whose main component is ozone (O3), i.e., substances of environmental concern, and are the cause of photochemical smog. In Japan, the environmental standard for photochemical oxidants is set at 0.06 ppm or less in one-hour values, but the current situation is that the standard value continues to be exceeded, and with the increasing worldwide awareness of global environmental conservation issues in recent years, there is a demand for immediate measures to reduce photochemical oxidants.

[0003] Therefore, as a technology to prevent the generation of photochemical smog, the present applicants have previously proposed (Patent Document 1) an aqueous paint composition that can be applied (coated) to areas exposed to the air to decompose ozone in the air and purify the air. The technique of Patent Document 1 claims that high ozone decomposition performance can be achieved by using a manganese oxide catalyst in combination with activated carbon. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2020-152871 A (Patent No. 6945938 A) Summary of the Invention [Problem to be solved by the invention]

[0005] However, coating films containing manganese oxide catalysts and activated carbon, which are ozone decomposition catalysts, have a problem of poor weather resistance. This is because when a coating film contains a manganese oxide catalyst, it absorbs light and generates a photocatalytic effect, which decomposes and destroys the coating film components, accelerating the deterioration of the coating film. Furthermore, in coating films that have an ozone decomposition effect due to the inclusion of a manganese oxide catalyst and activated carbon, it is thought that the oxygen generated by the ozone decomposition is one of the factors that accelerate the deterioration (oxidation deterioration) of the coating film.

[0006] Here, if an aqueous coating composition containing a manganese oxide catalyst and activated carbon is applied to a location where an air flow occurs, the ozone in the atmosphere can be efficiently decomposed by contact with the air flow, and the atmosphere can be purified. For example, in the case of an automobile, by applying the composition to the automobile radiator, the electric fan nearby, the grill shutter, and other locations where a large amount of air passes while the vehicle is running or due to the rotation of the fan, the ozone can be reduced to oxygen while the vehicle is running, and the atmosphere can be effectively purified. However, such structural components of automobiles, particularly exterior components, are sometimes exposed to light, and when a coating containing a manganese oxide catalyst and activated carbon is applied to them, the coating contains a manganese oxide catalyst that has photocatalytic properties, which makes it prone to a chalking phenomenon in which the resin near the manganese oxide catalyst deteriorates and the manganese oxide catalyst peels off from the resin.

[0007] Therefore, an object of the present invention is to provide an aqueous coating composition which is capable of forming a cured coating film which is resistant to chalking and has high weather resistance even when it contains a manganese oxide catalyst, a cured coating film thereof, and a coated article. [Means for solving the problem]

[0008] The aqueous coating composition of the invention of claim 1 contains water as a main component of the solvent, a manganese oxide catalyst as an ozone decomposition catalyst, activated carbon having ozone adsorption properties, an aqueous resin, and a dispersant, and the aqueous resin is ,strange Resistant acrylic resin or Fluorine Tree With fat There is something.

[0009] The manganese oxide catalyst used here may be any catalyst having a catalytic function for decomposing ozone. For example, a metal oxide catalyst such as manganese monoxide or manganese dioxide is used, but a manganese dioxide catalyst having high catalytic activity is preferred. As the activated carbon, for example, coconut shell activated carbon, petroleum pitch-based activated carbon, wood-based activated carbon, etc. are preferably used because they have a very high ozone adsorption specific surface area, and among them, coconut shell activated carbon is preferred. An aqueous resin (also called a water-based resin) refers to a water-soluble resin that can be dissolved in an aqueous solvent or a water-dispersible resin that can be dispersed in water.

[0010] The aqueous coating composition according to claim 1 Before The modified acrylic resin preferably has a glass transition temperature (glass transition point, Tg) in the range of -30°C or higher and 130°C or lower, more preferably -25°C or higher and 120°C or lower.

[0011] The fluororesin of the aqueous coating composition of the invention of claim 1 has a glass transition temperature (glass transition point, Tg) preferably in the range of -30°C or higher and 100°C or lower, more preferably in the range of -25°C or higher and 90°C or lower.

[0012] The aqueous resin of the aqueous coating composition of the invention of claim 2 is preferably blended in an amount of 20 parts by mass or more and 400 parts by mass or less, more preferably 25 parts by mass or more and 350 parts by mass or less, and even more preferably 30 parts by mass or more and 300 parts by mass or less, per 100 parts by mass of the total blend amount of the manganese oxide catalyst and the activated carbon.

[0013] The aqueous resin of the aqueous coating composition of the invention of claim 3 is preferably blended in a range of 30 parts by mass or more and 500 parts by mass or less, more preferably 40 parts by mass or more and 480 parts by mass or less, and even more preferably 45 parts by mass or more and 450 parts by mass or less, per 100 parts by mass of the manganese oxide catalyst.

[0014] The total amount of the manganese oxide catalyst and the activated carbon in the aqueous coating composition of the invention of claim 4 is preferably within the range of 25 parts by mass or more and 75 parts by mass or less, and more preferably 30 parts by mass or more and 65 parts by mass or less, per 100 parts by mass of the total amount of the manganese oxide catalyst, the activated carbon, and the aqueous resin.

[0015] The manganese oxide catalyst in the aqueous coating composition of the invention of claim 5 is preferably blended in an amount of 11 parts by mass or more and 900 parts by mass or less, more preferably 15 parts by mass or more and 800 parts by mass or less, and even more preferably 20 parts by mass or more and 700 parts by mass or less, per 100 parts by mass of the activated carbon.

[0016] The manganese oxide catalyst in the aqueous coating composition of the invention of claim 6 is preferably blended in an amount of 5 parts by mass or more and 65 parts by mass or less, more preferably 10 parts by mass or more and 60 parts by mass or less, and even more preferably 15 parts by mass or more and 55 parts by mass or less, relative to 100 parts by mass of the total blend amount of the manganese oxide catalyst, the activated carbon, and the aqueous resin.

[0017] The cured coating film of the invention of claim 7 contains a manganese oxide catalyst, activated carbon, and an aqueous resin, Strange Resistant acrylic resin or Fluorine Tree With fat There is something.

[0018] The cured coating film of the invention of claim 7 Before The modified acrylic resin preferably has a glass transition temperature (Tg) in the range of -30°C or higher and 130°C or lower, more preferably -25°C or higher and 120°C or lower.

[0019] The fluororesin of the cured coating film of the invention according to claim 7 has a glass transition temperature (Tg) preferably in the range of -30°C or higher and 100°C or lower, more preferably in the range of -25°C or higher and 90°C or lower.

[0020] The aqueous resin of the cured coating film of the invention of claim 8 preferably contains 20 parts by mass or more and 400 parts by mass or less, more preferably 25 parts by mass or more and 350 parts by mass or less, and even more preferably 30 parts by mass or more and 300 parts by mass or less, per 100 parts by mass of the total content of the manganese oxide catalyst and the activated carbon.

[0021] The aqueous resin of the cured coating film of the invention of claim 9 is contained in a range of 30 parts by mass or more and 500 parts by mass or less, more preferably 40 parts by mass or more and 480 parts by mass or less, and even more preferably 45 parts by mass or more and 450 parts by mass or less, per 100 parts by mass of the manganese oxide catalyst.

[0022] The total amount of the manganese oxide catalyst and the activated carbon in the cured coating film of the invention of claim 10 is preferably in the range of 25 parts by mass or more and 75 parts by mass or less, and more preferably 30 parts by mass or more and 65 parts by mass or less, per 100 parts by mass of the total content of the manganese oxide catalyst, the activated carbon, and the aqueous resin.

[0023] The manganese oxide catalyst of the cured coating film of the invention of claim 11 has a content of the activated carbon in the range of preferably 11 parts by mass or more and 900 parts by mass or less, more preferably 15 parts by mass or more and 800 parts by mass or less, and even more preferably 20 parts by mass or more and 700 parts by mass or less, per 100 parts by mass.

[0024] The manganese oxide catalyst of the cured coating film of the invention of claim 12 is preferably contained in a range of 5 parts by mass or more and 65 parts by mass or less, more preferably 10 parts by mass or more and 60 parts by mass or less, and even more preferably 15 parts by mass or more and 55 parts by mass or less, relative to 100 parts by mass of the total content of the manganese oxide catalyst, the activated carbon, and the aqueous resin.

[0025] The coated article of the present invention has a cured coating film formed on a substrate surface, the cured coating film including a manganese oxide catalyst, activated carbon, and an aqueous resin. Strange Resistant acrylic resin or Fluorine Tree With fat There is something. The coated article is a substrate (subject to be coated) on which a cured coating film containing a manganese oxide catalyst, activated carbon, and one or more aqueous resins selected from acrylic resin, modified acrylic resin, and fluororesin is formed by coating the substrate, regardless of whether it is a part, a finished product, or a finished product, and examples of the coated article include components of vehicles such as automobiles (particularly exterior components), building materials such as roofing materials and exterior walls, components of blowers and electrical appliances, agricultural and horticultural materials such as vinyl greenhouses and vinyl sheets, etc. More specific examples include filter members, honeycomb structure members, fans, etc. Effect of the Invention

[0026] The aqueous coating composition according to the invention of claim 1 contains a manganese oxide catalyst, activated carbon, an aqueous resin, and a dispersant, and contains water as a main component of a solvent. Change Resistant acrylic resin or Fluorine Tree Fat and This is what was done. The present inventors have carried out intensive experimental research into a technology for applying an aqueous coating composition containing a manganese oxide catalyst, activated carbon, an aqueous resin, a dispersant, and a solvent mainly composed of water to a substrate, and drying the composition to form a cured coating film that is resistant to chalking even when the coating film contains a manganese oxide catalyst. As a result, the inventors have found that the aqueous resin, which is a binder, Change Resistant acrylic resin or Fluorine Tree Fat and It has been found that by doing so, chalking resistance can be obtained, and thus the present invention has been completed.

[0027] In other words, depending on the type of polymer, there are differences in weaknesses against deterioration due to light, oxidation, moisture, etc., decomposition mechanisms (deterioration mechanisms), and deterioration factors. In addition, the deterioration mechanisms of polymers differ depending on the components contained in the coating film. There are complex factors involved in the deterioration of polymers, and the aqueous resin, which is the binder, Strange Resistant acrylic resin or Fluorine Tree With fat If such a component is present, even if the cured coating film contains a manganese oxide catalyst, chalking is unlikely to occur under environmental conditions where the film is exposed to light, and the film has high weather resistance (durability).

[0028] The aqueous coating composition according to the invention of claim 1 ,before The glass transition temperature of the modified acrylic resin is within the range of -30°C to 130°C. As a result of intensive experimental research, the present inventors ,strange The inventors have found that a highly weatherable acrylic resin having a glass transition temperature within the range of -30°C to 130°C has higher weather resistance, and have thus completed the present invention. That is, the glass transition temperature is within the range of -30℃ to 130℃. Change If the cured coating film is a water-resistant acrylic resin, chalking (whitening) is less likely to occur under environmental conditions where the coating film is exposed to light, even if the cured coating film contains a manganese oxide catalyst, and the weather resistance (durability) is higher. More preferably, the glass transition temperature is within the range of -25°C to 120°C.

[0029] In the aqueous coating composition according to the invention of claim 1, the glass transition temperature of the fluororesin is within the range of -30°C to 100°C. As a result of extensive experimental research, the present inventors have found that fluororesin having a glass transition temperature within the range of -30°C to 100°C has higher weather resistance, and have thus completed the present invention. That is, if the fluororesin has a glass transition temperature in the range of -30°C to 100°C, chalking (whitening) is less likely to occur under environmental conditions where the coating film is exposed to light, even if the cured coating film contains a manganese oxide catalyst, and the weather resistance (durability) is higher. More preferably, the glass transition temperature is in the range of -25°C to 90°C.

[0030] The aqueous coating composition according to the invention of claim 2 is one in which the aqueous resin is mixed in an amount preferably within the range of 20 to 400 parts by mass per 100 parts by mass of the total amount of the manganese oxide catalyst and the activated carbon. 。 strange Resin-resistant acrylic resin or fluororesin With fat When the blending amount of a certain aqueous resin is too high relative to the manganese oxide catalyst and activated carbon, the blending amount of the ozone-decomposing manganese oxide catalyst and activated carbon becomes relatively low, resulting in a decrease in ozone decomposition ability.On the other hand, when the blending amount of the aqueous resin is too high relative to the manganese oxide catalyst and activated carbon, the blending amount of the aqueous resin as a binder becomes relatively low, resulting in a brittle product that deteriorates quickly and has a decrease in chalking resistance. When the blending amount of the aqueous resin is within a range of preferably 20 parts by mass to 400 parts by mass relative to 100 parts by mass of the total amount of the manganese oxide catalyst and the activated carbon, both ozone decomposition property and weather resistance can be achieved, more preferably within a range of 25 parts by mass to 350 parts by mass, and further preferably within a range of 30 parts by mass to 300 parts by mass.

[0031] The aqueous coating composition according to the invention of claim 3 is one in which the aqueous resin is blended in an amount ranging from 30 to 500 parts by mass with respect to 100 parts by mass of the manganese oxide catalyst. 。 strange Resin-resistant acrylic resin or fluororesin With fatWhen the amount of a certain aqueous resin mixed with the manganese oxide catalyst is too high, the amount of the ozone-decomposing manganese oxide catalyst mixed with the manganese oxide catalyst and the activated carbon becomes relatively low, and the ozone decomposing performance due to the synergistic effect of the manganese oxide catalyst and the activated carbon decreases. On the other hand, when the amount of an aqueous resin mixed with the manganese oxide catalyst is too high, the concentration of the aqueous resin as a binder becomes relatively low and the concentration of the manganese oxide catalyst becomes relatively high, and the chalking resistance decreases. When the blending amount of the aqueous resin is within a range of preferably 30 parts by mass to 500 parts by mass relative to 100 parts by mass of the manganese oxide catalyst, ozone decomposability and weather resistance can be more effectively achieved, more preferably within a range of 40 parts by mass to 480 parts by mass, and even more preferably within a range of 45 parts by mass to 450 parts by mass.

[0032] The aqueous coating composition of the invention of claim 4 is one in which the total amount of the manganese oxide catalyst and the activated carbon is within the range of 25 to 75 parts by mass per 100 parts by mass of the total amount of the manganese oxide catalyst, the activated carbon, and the aqueous resin. If the concentrations of the ozone-decomposable manganese oxide catalyst and activated carbon, which are the coating film components, are too high, the blending ratio of the aqueous resin, which is the binder, becomes relatively low, resulting in fragility, rapid deterioration, and reduced weather resistance.On the other hand, if the concentrations of the ozone-decomposable manganese oxide catalyst and activated carbon are too low, the ozone decomposability decreases. When the blending amount of the manganese oxide catalyst and activated carbon is within a range of preferably 25 to 75 parts by mass relative to 100 parts by mass of the total amount of the manganese oxide catalyst, activated carbon, and aqueous resin, both ozone decomposition property and weather resistance can be achieved, and more preferably within a range of 30 to 65 parts by mass.

[0033] In the aqueous coating composition according to the invention of claim 5, the manganese oxide catalyst is blended in an amount within the range of 11 to 900 parts by mass per 100 parts by mass of the activated carbon. If the amount of manganese oxide catalyst is too high compared to the activated carbon, weather resistance will decrease. On the other hand, if the amount of manganese oxide catalyst is too low compared to the activated carbon, the amount of activated carbon will be relatively high and the activated carbon will be more likely to aggregate, resulting in decreased dispersibility and reduced coatability. When the amount of the manganese oxide catalyst is within a range of preferably 11 to 900 parts by mass relative to 100 parts by mass of activated carbon, it is possible to achieve both coatability and weather resistance, more preferably 15 to 800 parts by mass, and even more preferably 20 to 700 parts by mass.

[0034] The aqueous coating composition of the invention of claim 6 contains the manganese oxide catalyst in an amount ranging from 5 to 65 parts by mass per 100 parts by mass of the total amount of the manganese oxide catalyst, the activated carbon, and the aqueous resin. If the concentration of the manganese oxide catalyst, which is a coating component, is too high, the weather resistance will decrease, while if the concentration is too low, the ozone decomposition ability due to the synergistic effect of the manganese oxide catalyst and activated carbon will decrease. The manganese oxide catalyst is preferably contained in an amount of 5 to 65 parts by mass relative to 100 parts by mass of the total amount of the manganese oxide catalyst, the activated carbon, and the aqueous resin, which makes it possible to achieve both ozone decomposition property and weather resistance, more preferably in an amount of 10 to 60 parts by mass, and even more preferably in an amount of 15 to 55 parts by mass.

[0035] The cured coating film according to the invention of claim 7 includes a manganese oxide catalyst, activated carbon, and an aqueous resin, Strange Resistant acrylic resin or Fluorine Tree With fat There is something. The present inventors have carried out intensive experimental research into a technology for applying an aqueous coating composition containing a manganese oxide catalyst, activated carbon, an aqueous resin, a dispersant, and a solvent mainly composed of water to a substrate, and drying the composition to form a cured coating film that is resistant to chalking even when the coating film contains a manganese oxide catalyst. As a result, the inventors have found that the aqueous resin, which is a binder, Change Resistant acrylic resin or Fluorine Tree Fat andIt has been found that by doing so, chalking resistance can be obtained, and thus the present invention has been completed.

[0036] In other words, depending on the type of polymer, there are differences in weaknesses against deterioration due to light, oxidation, moisture, etc., decomposition mechanisms (deterioration mechanisms), and deterioration factors. In addition, the deterioration mechanisms of polymers differ depending on the components contained in the coating film. There are complex factors involved in the deterioration of polymers, and the aqueous resin, which is the binder, Strange Resistant acrylic resin or Fluorine Tree With fat If such a component is present, even if the cured coating film contains a manganese oxide catalyst, chalking (whitening) is less likely to occur under environmental conditions where the film is exposed to light, and the weather resistance (durability) is improved.

[0037] The cured coating film according to the invention of claim 7 has a glass transition temperature in the range of -30°C to 130°C. Change It is made of a highly resistant acrylic resin. As a result of intensive experimental research, the present inventors ,strange The inventors have found that a weather-resistant acrylic resin having a glass transition temperature within the range of -30°C to 130°C has higher weather resistance, and have thus completed the present invention. That is, the glass transition temperature is within the range of -30℃ to 130℃. Change If the cured coating film is a water-soluble acrylic resin, chalking (whitening) is less likely to occur under environmental conditions where the coating film is exposed to light, even if the cured coating film contains a manganese oxide catalyst, and the coating film has high weather resistance (durability). More preferably, the glass transition temperature is within the range of -25°C to 120°C.

[0038] The cured coating film according to the invention of claim 7 uses the fluororesin having a glass transition temperature within the range of -30°C to 100°C. As a result of extensive experimental research, the present inventors have found that fluororesin having a glass transition temperature within the range of -30°C to 100°C has higher weather resistance, and have thus completed the present invention. That is, if the fluororesin has a glass transition temperature in the range of -30°C to 100°C, chalking (whitening) is less likely to occur under environmental conditions where the coating film is exposed to light, and weather resistance (durability) is higher, even if the cured coating film contains a manganese oxide catalyst. More preferably, the glass transition temperature (Tg) is in the range of -25°C to 90°C.

[0039] The cured coating film according to the invention of claim 8 contains the aqueous resin in an amount ranging from 20 parts by mass to 400 parts by mass per 100 parts by mass of the total amount of the manganese oxide catalyst and the activated carbon. where ,strange Resin-resistant acrylic resin or fluororesin With fat When the blending amount of a certain aqueous resin is too high relative to the manganese oxide catalyst and activated carbon, the blending amount of the ozone-decomposing manganese oxide catalyst and activated carbon becomes relatively low, resulting in a decrease in ozone decomposition ability.On the other hand, when the blending amount of the aqueous resin is too high relative to the manganese oxide catalyst and activated carbon, the blending amount of the aqueous resin as a binder becomes relatively low, resulting in a brittle product that deteriorates quickly and has a decrease in chalking resistance. When the content of the aqueous resin is within a range of preferably 20 parts by mass to 400 parts by mass relative to 100 parts by mass of the total amount of the manganese oxide catalyst and the activated carbon, both ozone decomposition property and weather resistance can be achieved, more preferably within a range of 25 parts by mass to 350 parts by mass, and further preferably within a range of 30 parts by mass to 300 parts by mass.

[0040] The cured coating film according to the invention of claim 9 contains the aqueous resin in an amount ranging from 30 parts by mass to 500 parts by mass per 100 parts by mass of the manganese oxide catalyst. 。 strange Resin-resistant acrylic resin or fluororesin With fatWhen the amount of a certain aqueous resin mixed with the manganese oxide catalyst is too high, the amount of the ozone-decomposing manganese oxide catalyst mixed with the manganese oxide catalyst and the activated carbon becomes relatively low, and the ozone decomposing performance due to the synergistic effect of the manganese oxide catalyst and the activated carbon decreases. On the other hand, when the amount of an aqueous resin mixed with the manganese oxide catalyst is too high, the concentration of the aqueous resin as a binder becomes relatively low and the concentration of the manganese oxide catalyst becomes relatively high, and the chalking resistance decreases. The content of the aqueous resin is preferably within a range of 30 to 500 parts by mass relative to 100 parts by mass of the manganese oxide catalyst, more preferably within a range of 40 to 480 parts by mass, and even more preferably within a range of 45 to 450 parts by mass, in order to achieve a good balance between ozone decomposition property and weather resistance.

[0041] In the cured coating film according to the invention of claim 10, the total content of the manganese oxide catalyst and the activated carbon is within the range of 25 to 75 parts by mass per 100 parts by mass of the total amount of the manganese oxide catalyst, the activated carbon, and the aqueous resin. If the concentrations of the ozone-decomposable manganese oxide catalyst and activated carbon, which are the coating film components, are too high, the blending ratio of the aqueous resin, which is the binder, becomes relatively low, resulting in fragility, rapid deterioration, and reduced weather resistance.On the other hand, if the concentrations of the ozone-decomposable manganese oxide catalyst and activated carbon are too low, the ozone decomposability decreases. The content of the manganese oxide catalyst and activated carbon is preferably within a range of 25 to 75 parts by mass relative to 100 parts by mass of the total amount of the manganese oxide catalyst, activated carbon, and aqueous resin, so that both ozone decomposition property and weather resistance can be achieved, and more preferably within a range of 30 to 65 parts by mass.

[0042] The cured coating film according to an eleventh aspect of the present invention contains the manganese oxide catalyst in an amount within the range of 11 to 900 parts by mass per 100 parts by mass of the activated carbon. If the amount of manganese oxide catalyst is too high compared to the activated carbon, weather resistance will decrease. On the other hand, if the amount of manganese oxide catalyst is too low compared to the activated carbon, the amount of activated carbon will be relatively high and the activated carbon will be more likely to aggregate, resulting in decreased dispersibility and reduced coatability. The manganese oxide catalyst content is preferably within a range of 11 to 900 parts by mass relative to 100 parts by mass of activated carbon, and can provide both coatability and weather resistance, more preferably within a range of 15 to 800 parts by mass, and even more preferably within a range of 20 to 700 parts by mass.

[0043] The cured coating film according to the invention of claim 12 contains the manganese oxide catalyst in an amount ranging from 5 parts by mass to 65 parts by mass per 100 parts by mass of the total amount of the manganese oxide catalyst, the activated carbon, and the aqueous resin. If the concentration of the manganese oxide catalyst, which is a coating component, is too high, the weather resistance will decrease, while if the concentration is too low, the ozone decomposition ability due to the synergistic effect of the manganese oxide catalyst and activated carbon will decrease. The manganese oxide catalyst content is preferably within a range of 5 to 65 parts by mass relative to 100 parts by mass of the total amount of the manganese oxide catalyst, activated carbon, and aqueous resin, so that both ozone decomposition property and weather resistance can be improved, more preferably within a range of 10 to 60 parts by mass, and even more preferably within a range of 15 to 55 parts by mass.

[0044] The coated article of the present invention has a cured coating film formed on a substrate surface, the cured coating film including a manganese oxide catalyst, activated carbon, and an aqueous resin. Strange Resistant acrylic resin or Fluorine Tree With fat There is something. The present inventors have carried out intensive experimental research into a technology for applying an aqueous coating composition containing a manganese oxide catalyst, activated carbon, an aqueous resin, a dispersant, and a solvent mainly composed of water to a substrate, and drying the composition to form a cured coating film that is resistant to chalking even when the coating film contains a manganese oxide catalyst. As a result, the inventors have found that the aqueous resin, which is a binder, Change Resistant acrylic resin or Fluorine Tree Fat andIt has been found that by doing so, chalking resistance can be obtained, and thus the present invention has been completed.

[0045] In other words, depending on the type of polymer, there are differences in weaknesses against deterioration due to light, oxidation, moisture, etc., decomposition mechanisms (deterioration mechanisms), and deterioration factors. In addition, the deterioration mechanisms of polymers differ depending on the components contained in the coating film. There are complex factors involved in the deterioration of polymers, and the aqueous resin, which is the binder, Strange Resistant acrylic resin or Fluorine Tree With fat If such a component is present, even if the cured coating film contains a manganese oxide catalyst, chalking (whitening) is less likely to occur under environmental conditions where the film is exposed to light, and the weather resistance (durability) is improved. [Brief description of the drawings]

[0046] [Figure 1] FIG. 1 is a schematic diagram for explaining a method of evaluation testing for evaluating the ozone decomposition property of a cured coating film of an aqueous coating composition according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram for explaining an example of a coated article to which the aqueous coating composition of the embodiment of the present invention is applied. [Diagram 3] FIG. 3 is a schematic diagram for explaining another example of a coated article to which the aqueous coating composition according to an embodiment of the present invention is applied. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0047] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. In the embodiments, the same symbols and the same reference characters shown in the drawings indicate parts having the same or corresponding functions, and therefore, redundant explanations thereof will be omitted here.

[0048] [Embodiment Mode] First, the aqueous coating composition according to the embodiment of the present invention will be described. The aqueous coating composition according to the embodiment of the present invention is a blend of a manganese oxide catalyst, activated carbon, a dispersant, a water-based resin, a pH adjuster, and a solvent whose main component is water.

[0049] Manganese oxide (Mn x O y As the manganese oxide, for example, manganese monoxide (MnO) catalysts, manganese dioxide (manganese (IV) oxide) catalysts, spinel-type manganate metals, etc. can be used as the manganese oxide. In particular, manganese dioxide (MnO2) catalysts are preferred because they have high ozone decomposition catalytic activity and can form a coating film with high ozone decomposition properties. Note that manganese oxide, generally known as manganese dioxide, is a non-stoichiometric compound, and in reality, MnO x The composition is approximately (x=1.93~2). Manganese dioxide may be natural or may be produced by electrolysis or chemical synthesis, and may be amorphous or may have a crystalline structure. Examples of the crystalline structure of manganese dioxide include alpha, beta, gamma, and delta types, and more preferably α-manganese dioxide (cryptomelane type). Manganese dioxide may also have an amorphous structure. The manganese oxide catalyst may be based on manganese oxide (e.g., manganese dioxide) and contain a promoter such as NiO, CuO, AgO, etc., or may contain calcium oxide that adsorbs moisture. The manganese oxide catalyst preferably has a manganese oxide (e.g., manganese dioxide) content of 70% or more, more preferably 80% or more.

[0050] Manganese oxide catalysts, such as manganese dioxide catalysts, have a specific surface area of ​​100 m2 or more, as measured by the BET method for N2 adsorption. 2 / g or more, 400m 2It is preferable to use a surface area of ​​less than 100 m2 / g. If the surface area is too large, aggregation is likely to occur, resulting in reduced dispersibility and dispersion stability. If the dispersibility is reduced, clogging of the coating device occurs, paint particles (aggregates) are formed on the coating surface, impairing the film-forming and adhesion properties of the coating, and coating film chipping, peeling, and catalyst drop-off are likely to occur. Furthermore, if the dispersion stability is reduced, storage stability cannot be ensured. On the other hand, if the surface area is too small, the desired high ozone decomposition performance cannot be obtained. If the specific surface area measured by the BET method for N2 adsorption is less than 100 m2, the desired high ozone decomposition performance cannot be obtained. 2 / g or more, 400m 2 A manganese oxide catalyst having a specific surface area of ​​150 m2 or less by the BET method can provide good dispersibility and dispersion stability, good film-forming and adhesion properties of the coating film, is less susceptible to catalyst detachment, and can provide high ozone decomposition performance. In addition, the coating composition can have good storage stability. More preferably, the specific surface area by the BET method is 150 m2 or less. 2 / g or more, 350m 2 / g or less, and more preferably 180m 2 / g or more, 300m 2 / g or less.

[0051] The "specific surface area" is based on the gas adsorption method (BET method). The BET (Brunauer-Emmett-Teller) method is a method in which molecules with a known adsorption area are adsorbed onto the particle surface at liquid nitrogen temperature, and the specific surface area of ​​the sample is calculated from the amount of adsorption. This method relies on the low-temperature physical adsorption of an inert gas such as nitrogen.

[0052] Furthermore, it is preferable to use a manganese oxide catalyst such as a manganese dioxide catalyst having a median diameter (average particle diameter) in the range of 1 to 20 μm. If the particle diameter is too large, the surface area will be small, and the desired high ozone decomposition performance will not be obtained. In addition, the film-forming property, film thickness, and adhesion of the coating film will decrease, and the coating film will peel off and the catalyst will fall off easily. On the other hand, if the particle diameter is too small, aggregation will occur easily, and dispersibility and dispersion stability will decrease. If the dispersibility decreases, paint bumps (aggregates) will occur on the coating film surface, impairing the film-forming property and adhesion of the coating film, and the coating film will be chipped, peeled off, and the catalyst will fall off easily. In addition, if the dispersion stability decreases, storage stability cannot be ensured. If the manganese oxide catalyst has a median diameter (average particle diameter) in the range of 1 to 20 μm, it is possible to improve dispersibility and dispersion stability, and the coating film will have good film-forming property and adhesion, and the catalyst will not easily fall off, and high ozone decomposition performance can be exhibited for a long time. Furthermore, good storage stability of the coating composition can be obtained.The median diameter (average particle diameter) is more preferably within the range of 3 to 18 μm, and even more preferably within the range of 5 to 15 μm.

[0053] According to the definition of terms in the text and explanation of JIS Z 8901 "Test powders and test particles," the "median diameter" refers to the number of particles larger than a certain particle diameter in the particle size distribution of a powder (or The particle size (diameter) when the particle size (or mass) of a powder is 50% of that of the whole powder, i.e., the particle size of the powder that is 50% oversized. It is usually called the median diameter or 50% particle size. 50 By definition, the size of a particle group is expressed by the average particle size and the median size, but here, the value is the value displayed in the product description and measured by the laser diffraction / scattering method. This "median size measured by the laser diffraction / scattering method" refers to the particle size (D 50) Note that the above values ​​are not strict and there are differences between products, and including errors due to measurement, etc., it is not denied that there may be an error of about 10% or less. From the viewpoint of this error, it shows a normal distribution, and since the particle size shows a normal distribution, even if the median diameter is considered to be approximately equal to the average particle size, the difference between the two is within a few percent, and is considered to be an error.

[0054] As the activated carbon, sawdust, wood chips, charcoal, bamboo charcoal, coal (lignite, brown coal, bituminous coal), petroleum-based (petroleum pitch, oil carbon, etc.), walnut shell charcoal, coconut shell charcoal, resin (phenolic resin, epoxy resin, etc.), rayon, etc. can be used, but preferably, the carbon content is 90% or more. Among them, coconut shell charcoal, petroleum pitch-based activated carbon, wood-based activated carbon, etc., which have a high ozone adsorption specific surface area, are preferred. As the coconut shell charcoal, coconut shell charcoal such as coconut, oil palm, and sago palm, which have a high carbon content, is preferred. In addition, the activated carbon may be one which supports an organometallic complex with cobalt, iron, etc. as a central metal.

[0055] Activated carbon such as coconut shell charcoal has a specific surface area of ​​500 m2 or more, as measured by the BET method for N2 adsorption. 2 / g or more, 3000m 2 It is preferable to use a surface area of ​​less than 500 m2 / g. If the surface area is too large, aggregation is likely to occur, resulting in reduced dispersibility and dispersion stability. If the dispersibility is reduced, clogging of the coating device occurs, paint particles (aggregates) are formed on the coating surface, impairing the film-forming and adhesive properties of the coating, and the coating is likely to chip, peel, or fall off. If the dispersion stability is reduced, storage stability cannot be ensured. On the other hand, if the surface area is too small, the desired high ozone decomposition performance cannot be obtained. If the BET specific surface area measured by the BET method for N2 adsorption is less than 500 m2, the desired high ozone decomposition performance cannot be obtained. 2 / g or more, 3000m 2 Activated carbon having a specific surface area of ​​600 m2 or less by the BET method can provide good dispersibility and dispersion stability, good film-forming and adhesion properties of the coating film, and is less likely to fall off, resulting in a sustained high ozone decomposition performance. In addition, the coating composition can provide good storage stability. More preferably, the specific surface area by the BET method is 600 m2 or less.2 / g or more, 2500m 2 / g or less, and more preferably 900m 2 / g or more, 2000m 2 The total pore volume of this activated carbon is calculated from the amount of nitrogen adsorbed when the relative pressure P / P0 is 1.0 in the nitrogen BET nitrogen adsorption isotherm, and is, for example, 0.1 cm 3 / g~1.5cm 3 / g, and more preferably in the range of 0.2 cm 3 / g~1.0cm 3 / g. The average pore size of this activated carbon (calculated by total pore volume / BET specific surface area×4) is, from the viewpoints of ozone adsorption ability and prevention of clogging due to particulate matter in the air, for example, in the range of 0.3 to 10 nm, and more preferably in the range of 0.5 to 5 nm.

[0056] Furthermore, it is preferable to use activated carbon such as coconut shell charcoal having a median diameter (average particle diameter) in the range of 1 to 20 μm. If the particle diameter is too large, the surface area will be small, and the desired high ozone decomposition performance will not be obtained. In addition, the film-forming property and adhesion of the coating film will decrease, and the coating film will peel off and the activated carbon will fall off easily. On the other hand, if the particle diameter is too small, aggregation will occur easily, and dispersibility and dispersion stability will decrease. If the dispersibility decreases, paint bumps (aggregates) will occur on the coating film surface, and the coating film forming property, coating film thickness, and adhesion will decrease, and the coating film will be chipped, peeled off, and the catalyst will fall off easily. In addition, if the dispersion stability decreases, storage stability cannot be ensured. If the activated carbon has a median diameter (average particle diameter) in the range of 1 to 20 μm, it is possible to improve dispersibility and dispersion stability, and the coating film will have good film-forming property and adhesion, and the catalyst will not easily fall off, and high ozone decomposition performance can be exhibited for a long time. More preferably, the median diameter (average particle diameter) is within the range of 3 to 18 μm, and even more preferably, within the range of 5 to 15 μm.

[0057] In addition, as the dispersant to be blended in the aqueous coating composition of the present embodiment, for example, a polyacrylate-based dispersant can be used. The polyacrylate-based dispersant is, for example, a polyacrylate salt, or a dispersant based on an acrylic skeleton or a modified acrylic skeleton. Note that the polyacrylate-based dispersant also includes modified polyacrylate-based ones.

[0058] In particular, polyacrylate-based dispersants can prevent aggregation (deflocculation) of the manganese oxide-based catalyst and activated carbon, and can finely and highly disperse the manganese oxide-based catalyst and activated carbon in the paint, while also improving the dispersion stability.

[0059] That is, since the manganese oxide catalyst and activated carbon having ozone decomposition performance are in particulate or powder form, in order to make the manganese oxide catalyst and activated carbon in particulate or powder form into paint, the manganese oxide catalyst and activated carbon need to be uniformly dispersed in the resin, solvent, and other components that make up the paint, but the manganese oxide catalyst and activated carbon, which have a large surface area capable of absorbing a large amount of ozone, tend to aggregate, and in particular, activated carbon has pores, so that the resin (organic matter) and manganese oxide catalyst, which are paint components, adhere to the pores, making it easy for aggregation to occur. If the manganese oxide catalyst and activated carbon have low dispersibility and are highly aggregated, aggregation gelation and an increase in viscosity occur, making it difficult to make into paint, or clogging of the piping, pump, etc. of the application device occurs during application. Even if it is possible to make into paint, bumps and roughness will occur in the coating film, and if it is applied to cover the base material, the coating film will become thick, lacking in film-forming and adhesion properties, and poor appearance. Furthermore, if there is a lot of aggregation of the manganese oxide catalyst or activated carbon, the amount of ozone that can be adsorbed is small, and high ozone decomposition performance cannot be obtained. Naturally, if the dispersibility of the manganese oxide catalyst or activated carbon is low and there is a lot of aggregation, the storage stability as a paint is lacking due to aggregation gelation and increased viscosity, and long-term storage is difficult. Therefore, when using particulate or powdered manganese oxide catalyst and activated carbon to make them into paints, a high-dispersion technology is required to prevent aggregation of the manganese oxide catalyst and activated carbon.

[0060] By adding a polyacrylate-based dispersant, the manganese oxide catalyst and activated carbon can be sufficiently deaggregated and stabilized. That is, the manganese oxide catalyst and activated carbon can be finely and highly dispersed, and the degree of dispersion measured by a grind gauge in accordance with JISK 5600 and JISK 5400 (1990) is, for example, greater than the maximum particle diameter (D max In addition, the 90% cumulative particle diameter (D 90 ) and can be reduced to 10 μm or less.

[0061] In particular, in a coating film formed from an aqueous coating composition in which a manganese oxide catalyst and activated carbon are highly dispersed to fine particle size by a polyacrylate dispersant, bumps and roughness are suppressed, excellent film-forming properties and adhesion to the substrate are ensured, and good smoothness, i.e., good appearance, is obtained. Because the coating film is less likely to develop bumps and has excellent film-forming properties, it is possible to form a thin film that can adequately cover the substrate even with a dry film thickness of 5 μm or less. In addition, in the cured coating film obtained by applying the aqueous coating composition in which the manganese oxide catalyst and activated carbon are highly dispersed in fine particle size by the polyacrylate dispersant to a substrate and drying, the manganese oxide catalyst and activated carbon are highly dispersed in fine particle size, so that the amount of ozone adsorption by the manganese oxide catalyst and activated carbon can be increased, and high ozone decomposition performance can be exhibited. In particular, since the manganese oxide catalyst and activated carbon can be highly dispersed with a small amount of polyacrylate dispersant, the polyacrylate dispersant does not inhibit the adsorption of ozone to the manganese oxide catalyst and activated carbon, and even a small amount of the manganese oxide catalyst and activated carbon can adsorb a large amount of ozone. Therefore, the cured coating film formed from this aqueous coating composition can exhibit excellent ozone decomposition performance in a thin film. In addition, in the aqueous coating composition using such a polyacrylate-based dispersant, the dispersion stability of the manganese oxide catalyst and activated carbon is high and they do not re-aggregate, so that the storage stability is high and long-term storage is possible. For example, even after storage for one month, precipitation separation due to aggregation is unlikely to occur, and the storage stability is high.

[0062] In addition, the polyacrylate-based dispersant preferably has a weight average molecular weight in the range of 5000 to 30000. The higher the molecular weight, the more adsorption sites there are in the molecule, so that even at low concentrations, the manganese oxide catalyst and activated carbon can be adsorbed at multiple points to prevent aggregation. However, if the molecular weight is too high, the compatibility and affinity with the paint components decreases, making it difficult to make the paint. On the other hand, if the molecular weight is too low, the number of adsorption points is small, making the dispersibility of the manganese oxide catalyst and activated carbon poor. If the amount of the polyacrylate-based dispersant is increased to increase the dispersibility, the adsorption of ozone to the manganese oxide catalyst and activated carbon will be inhibited, and the ozone decomposition performance will be reduced. If the weight average molecular weight of the polyacrylate-based dispersant is in the range of 5000 to 30000, it will have good compatibility with other materials and can ensure high dispersibility of the manganese oxide catalyst and activated carbon. More preferably, the weight average molecular weight is in the range of 6,000 to 28,000, and even more preferably, the weight average molecular weight is in the range of 7,000 to 25,000. The weight average molecular weight (Mw) is measured by gel permeation chromatography (GPC) and is calculated by converting a chromatogram measured by GPC into the molecular weight of standard polystyrene.

[0063] In addition, it is preferable to use a polyacrylate-based dispersant having an acid value in the range of 1 to 50. If the acid value is too high, the adsorption property will be poor depending on the polarity of other materials, for example, additives such as pigments. Furthermore, it is preferable to use this polyacrylate-based dispersant having a hydrogen ion exponent in the range of pH4 to pH9. If a dispersant outside this range is used, the dispersibility of the paint components will be poor depending on the type of additives, for example, pigments. If the hydrogen ion exponent is in the range of pH4 to pH9, the dispersion stability of the paint components can be ensured regardless of the type of blended materials. More preferable acid values ​​are in the range of 3 to 48, and even more preferable are in the range of 5 to 45. More preferable hydrogen ion exponent is in the range of pH4.5 to pH9, and even more preferable are in the range of pH5 to pH9. The acid value is measured using a neutralization titration method in accordance with JIS K 0070. The hydrogen ion exponent of the polyacrylate dispersant is measured (liquid temperature 25°C) in a diluted solution (emulsion, dispersion, aqueous solution) with a concentration of about 1% to 99%.

[0064] As such polyacrylate-based dispersants, commercially available products such as DESPERBYK from BYK-Chemie, EFKA from Ciba Specialty Chemicals and EFKA ADDITIVES BV, DISPARLON from Kusumoto Chemicals, and SN Thickener from SANNOPKO can be used. The polyacrylate-based dispersant can provide high dispersion and dispersion stability to the manganese oxide catalyst and activated carbon by, for example, preventing aggregation (deaggregation) of the manganese oxide catalyst and activated carbon due to adsorption caused by electrical repulsion of the polyacrylate against the manganese oxide catalyst and activated carbon, and steric hindrance caused by the anchor group or polymer chain of the polyacrylate, thereby stabilizing the manganese oxide catalyst and activated carbon at fine particle sizes, etc. In particular, the high molecular weight of the polyacrylate-based dispersant has multiple adsorption sites, so that even at a low concentration, it is adsorbed to the manganese oxide catalyst and activated carbon, enabling high dispersion of the manganese oxide catalyst and activated carbon, and since it does not require use at a high concentration, it is difficult to inhibit the adsorption of ozone to the manganese oxide catalyst and activated carbon.

[0065] However, when carrying out the present invention, other dispersants can be used as long as they are capable of highly dispersing the manganese oxide catalyst and activated carbon. The amount of the dispersant blended is preferably within a range of 1.5 to 75 parts by mass, more preferably within a range of 2 to 60 parts by mass, and even more preferably within a range of 2.5 to 50 parts by mass, relative to 100 parts by mass of the total amount of the manganese oxide catalyst and the activated carbon. Within the above range, both high storage stability and ozone decomposition property can be achieved.

[0066] The pH adjuster may be any that can adjust the hydrogen ion exponent to a predetermined pH (e.g., pH 7 to pH 12) during paint preparation, and examples of such pH adjusters include low-boiling amines such as triethylamine (TEA), ammonia, and dimethylaminoethanol. Neutralization with such pH adjusters prevents a decrease in viscosity of the paint composition and inhibits the settling of the manganese oxide catalyst and activated carbon. This maintains the high dispersibility of the manganese oxide catalyst and activated carbon, improving the coatability.

[0067] Furthermore, the solvent mainly composed of water is not limited to one consisting of water alone, i.e., one in which water is 100% by mass of the total solvent, but may be one in which water is more than 50% by mass of the total solvent, preferably 75% by mass or more, more preferably 90% by mass or more, and even more preferably 95% by mass or more, and may contain a small amount of organic solvent. Note that, for example, ion-exchanged water can be used as the water.

[0068] The aqueous resin to be blended in the aqueous coating composition of this embodiment is one or more of acrylic resin, modified acrylic resin, and fluororesin.

[0069] In particular, the acrylic resin preferably has a glass transition temperature (Tg) in the range of -30°C to 130°C, more preferably -25°C to 120°C, even more preferably -25°C to 90°C, and particularly preferably -20°C to 70°C. The glass transition temperature (Tg) is measured by differential scanning calorimetry (DSC).

[0070] Here, the acrylic resin broadly includes acrylic resin and methacrylic resin, and refers to a homopolymer or copolymer of (meth)acrylic acid (meaning acrylic acid or methacrylic acid; the same applies below) and a (meth)acrylic acid ester, or a copolymer of these monomers copolymerizable with (meth)acrylic acid, etc. Examples of the (meth)acrylic acid ester include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, p) n-butyl acrylate, isobutyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, ethylhexyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 2,2-bis(hydroxymethyl)ethyl (meth)acrylate, 3-chloro-2-hydroxypropyl (meth)acrylate, glycidyl (meth)acrylate, aminoethyl (meth)acrylate, aminopropyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, methoxyethyl (meth)acrylate, methoxypropyl (meth)acrylate, methoxybutyl (meth)acrylate, and stearyl (meth)acrylate.

[0071] As the monomer copolymerizable with (meth)acrylic acid, etc., a monomer having an ethylenically unsaturated group is preferable, and examples thereof include ethylene, propylene, butylene, butadiene, styrene, α-methylstyrene, vinylphenol, vinyl chloride, vinylidene chloride, vinyl acetate, vinyl pivalate, vinyl benzoate, vinyl alcohol, allyl alcohol, crotonic acid, itaconic acid, maleic acid, fumaric acid, (meth)acrylamide, N-methylol acrylamide, N-butoxymethylol (meth)acrylamide, (meth)acrylonitrile, etc. The copolymerization method in this case is generally emulsion polymerization, but is not limited thereto. In addition, in the case of an acid, its alkali metal salt, alkaline earth metal salt, etc. may be used.

[0072] The modified acrylic resin is a modified acrylic resin, for example, a urethane-modified, epoxy-modified, phenol-modified, melamine-modified (meth)acrylic acid polymer obtained by modifying a polymer or copolymer of (meth)acrylic acid with a urethane resin, an epoxy resin, a phenol resin, a melamine resin, etc., and examples of the polymer that can be used include urethane-modified (meth)acrylic resin, epoxy-modified (meth)acrylic resin, phenol-modified (meth)acrylic resin, and melamine-modified (meth)acrylic resin. The modified acrylic resin is preferably one in which the proportion of structural units constituting the acrylic resin exceeds 50% by mass relative to 100% by mass of all structural units constituting the resin, and the modified product is preferably one in which the proportion of structural units derived from the modified components is less than 50% by mass.

[0073] The modified acrylic resin preferably has a glass transition temperature (Tg) in the range of -30°C to 130°C, more preferably -25°C to 110°C, even more preferably -25°C to 80°C, and particularly preferably -20°C to 70°C.

[0074] Furthermore, examples of fluororesin that can be used include polytetrafluoroethylene (PTFE), tetrafluoroethylene-perfluoro(alkyl vinyl ether) copolymer (PFA), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), tetrafluoroethylene-hexafluoropropylene-perfluoro(alkyl vinyl ether) copolymer, tetrafluoroethylene-ethylene copolymer, polyvinylidene fluoride, polychlorotrifluoroethylene, and chlorotrifluoroethylene-ethylene copolymer.

[0075] The fluororesin preferably has a glass transition temperature (Tg) in the range of -30°C to 100°C, more preferably -25°C to 90°C, even more preferably -25°C to 80°C, and particularly preferably -20°C to 50°C.

[0076] It is preferable to use these acrylic resins, modified acrylic resins, and fluororesins whose median particle diameter (average particle diameter) is within the range of 50 to 150 nm. If it is within this range, the dispersibility of the resin content in water is high, the film-forming property and uniformity of the coating film are good, and the coating film can exhibit good adhesion to substrates such as metals. More preferably, the median diameter (average particle diameter) is within the range of 60 to 140 nm, and even more preferably within the range of 70 to 130 nm.

[0077] Furthermore, it is preferable that these acrylic resins, modified acrylic resins, and fluororesins are weakly alkaline, with a hydrogen ion exponent in the range of pH 7 to pH 9 (measurement of a resin dilution (emulsion, dispersion, aqueous solution) with a resin concentration of about 1% to 99% (liquid temperature 25°C)). This allows the resin to be highly dispersible in water, forming a dense coating film with good film-forming properties and uniformity, and also improving adhesion to substrates such as metals.

[0078] These aqueous resins, such as acrylic resins, modified acrylic resins, and fluororesins, are usually formulated in the form of a water-soluble resin dissolved or dispersed in an aqueous solvent (aqueous resin solution), emulsion, dispersion, aqueous varnish, aqueous sol, etc. The original meaning of "emulsion" is a liquid in which liquid particles are in the form of colloidal particles or coarser particles in a milky state (dispersion system) (Nagakura Saburo et al., ed., Iwanami Physics and Chemistry Dictionary (5th Edition), p. 152, published by Iwanami Shoten Co., Ltd. on February 20, 1998), but in this specification, the term "emulsion" is used in a broader sense as "a liquid in which solid or liquid particles are dispersed."

[0079] Incidentally, when carrying out the present invention, it is also possible to compound pigments such as coloring pigments, extender pigments, anti-rust pigments, functional pigments, etc., as well as additives for improving the coatability and coating performance, depending on the purpose and use of the water-based paint other than ozone decomposition, for example, for rust prevention or chipping resistance.

[0080] Examples of the coloring pigment that can be used in this case include carbon black, titanium oxide, iron oxide, zinc oxide, organic azo chelate pigments, insoluble azo pigments, condensed azo pigments, diketopyrrolopyrrole pigments, benzimidazolone pigments, phthalocyanine pigments, indigo pigments, perinone pigments, perylene pigments, dioxane pigments, quinacridone pigments, isoindolinone pigments, metal complex pigments, yellow lead, yellow iron oxide, red iron oxide, and titanium dioxide.

[0081] Examples of anti-rust pigments that can be used include zinc phosphate, zinc phosphite, aluminum polyphosphate, aluminum tripolyphosphate, zinc calcium molybdate, zinc orthophosphate, zinc polyphosphate, zinc molybdate, zinc phosphomolybdate, aluminum phosphomolybdate, zinc oxide, zinc phosphosilicate, aluminum zinc phosphate, calcium zinc phosphate, calcium zinc cyanamide, barium metaborate, magnesium aminophosphate, etc. From the viewpoint of environmental protection, anti-rust pigments that do not contain harmful heavy metals such as chromium are desirable. The content of such an anti-rust pigment in the coating film components is preferably 30 mass % or less, more preferably 20 mass % or less. If the content is within this range, the stability of the coating composition is also good.

[0082] Examples of extender pigments that can be used include talc, calcium carbonate, barium sulfate, calcium sulfate, mica, clay, silica, diatomaceous earth, alumina, baryta, silicon dioxide, etc. In particular, the use of talc forms many layers stacked together in the coating film, and the denseness of the layers formed by the arrangement of the talc can prevent the intrusion of corrosive factors.

[0083] Examples of additives that can be used include viscosity adjusters, film-forming aids, dispersants that mainly disperse pigments, defoamers, fillers, plasticizers, anti-sagging agents, film-forming aids, thixotropic agents, leveling agents, pH adjusters, neutralizing agents, UV absorbers, UV stabilizers, anti-settling agents, adhesion promoters, curing catalysts, neutralizing agents, driers (desiccant), stabilizers, and surface conditioners (coating surface conditioners).

[0084] For example, as a dispersant that mainly disperses pigments better, a polycarboxylic acid-based dispersant or the like can be used. The defoaming agent may be, for example, a silicone or acrylic defoaming agent, and the addition of such an defoaming agent can prevent the aqueous coating composition from becoming non-uniform due to the generation of fine bubbles during mixing to prepare the coating composition, and can adjust the viscosity and flowability. In addition, defoaming can prevent the generation of rust due to the intrusion of moisture from air bubbles, and can improve rust prevention. As the dryer (desiccant), for example, a metal dryer (metal desiccant) such as cobalt naphthenate or lead naphthenate can be used. By adding such a dryer, drying can be promoted at the stage when the aqueous paint composition is applied to form a coating film, and further polymerization of the aqueous resin to form a dense coating film can be promoted. As the stabilizer, for example, an alkanolamine derivative (diisopropanolamine, ethanolamine, diethanolamine, triisopropanolamine, triethanolamine) can be used, and when such a stabilizer is added, the fluidity, viscosity, dispersibility, etc. can be adjusted to stabilize the paint. The alkanolamine derivative may also function as an initial rust inhibitor.

[0085] Here, an example of a method for producing an aqueous coating composition according to the present embodiment, which contains the manganese oxide catalyst, activated carbon, a dispersant, one or more aqueous resins selected from acrylic resins, modified acrylic resins, and fluororesins, a pH adjuster, and a solvent mainly composed of water, will be described.

[0086] First, a dispersion step is carried out in which a solvent containing water as a main component, a manganese oxide catalyst, activated carbon, and a dispersant are mixed together, and the mixed materials are dispersed by a stirrer. Next, a neutralization step is carried out by adding a pH adjuster (neutralizer) to the mixture obtained by mixing and dispersing the manganese oxide catalyst, activated carbon, and dispersant in water in the dispersion step. Furthermore, the mixture neutralized in the neutralization step is mixed with at least one water-based resin selected from acrylic resin, modified acrylic resin, and fluororesin, and the mixture is mixed and dispersed in a mixer to form a paint. This produces an aqueous coating composition according to the present embodiment, which contains a manganese oxide catalyst, activated carbon, a dispersant, one or more aqueous resins selected from acrylic resins, modified acrylic resins, and fluororesins, a pH adjuster, and water as a solvent.

[0087] Examples of the agitator (mixing and dispersing machine) used in the dispersion process and paint production process include ball mills, bead mills, high-pressure injectors, dissolvers, Banbury mixers, planetary mixers, butterfly mixers, spiral mixers, roll mills, sand mills, paint shakers, grain mills, high-speed impeller mills, open kneaders, vacuum kneaders, attritors, dispersers, homomixers, homogenizers, colloid mills, microfluidizers, sonolators, and cavitrons. Preferably, a bead mill or roll mill can disperse the manganese oxide catalyst and activated carbon to a predetermined fine size with a small amount of energy. If a pigment is to be blended as necessary, the pigment may be mixed in the dispersion process.

[0088] In the neutralization step, a mixture of the manganese oxide catalyst, activated carbon, water, and dispersant is neutralized by mixing a pH adjuster to adjust the hydrogen ion exponent therein to preferably within a range of pH 7 to pH 12, more preferably pH 8 to pH 11.5, and even more preferably pH 9.5 to pH 11. This prevents the paint components from settling due to a decrease in the viscosity of the paint composition, enables uniform dispersion and stabilization of the paint, and ensures applicability and uniform coating performance after application. In the paint preparation process, the neutralized mixture is mixed with one or more aqueous resins selected from acrylic resin, modified acrylic resin, and fluororesin, and then mixed and dispersed with a stirrer. If additives are to be added as required, they may be mixed in this paint preparation process. When carrying out the present invention, the method for producing the aqueous coating composition is not limited to the above-mentioned method.

[0089] The aqueous coating composition thus prepared can be applied to a desired coating portion of a substrate (subject to be coated, object to be coated) in any coating amount, thickness and coating form by known coating methods, such as air spraying, showering, spraying, roll coating, curtain flow coating, die coating, brushing, dipping, shibori (squeezing), knife coater, bar coating, electrostatic coating, etc. The aqueous coating composition applied to the substrate is cured by natural drying or drying and baking in a drying oven, or, if necessary, by heat drying at a predetermined temperature for a predetermined time, or forced drying in a dryer, whereby the water and solvent are evaporated and volatilized, forming a cured coating film (coating layer) on the surface of the applied substrate. The aqueous coating composition of this embodiment may be applied directly to the desired application site (e.g., radiator, fan, etc.) and dried to form a cured coating film directly on the application site, or it may be applied to a substrate such as a vinyl chloride sheet (wrapping sheet) and dried to form a cured coating film on the sheet, and the sheet with the cured coating film attached may be attached to the desired application site (e.g., vehicle roof, vehicle interior parts), etc. Application to a substrate such as a vinyl chloride sheet (wrapping sheet) and dried to form a cured coating film on the substrate (sheet with cured coating film) is possible without application equipment or drying equipment, and does not require capital investment.

[0090] The aqueous coating composition of the present embodiment, which contains a manganese oxide catalyst, activated carbon, a dispersant, one or more aqueous resins selected from acrylic resin, modified acrylic resin and fluororesin, a pH adjuster and a solvent mainly composed of water, is applied to the surface of a substrate (an object to be coated, an object to be painted), and the aqueous coating composition applied to the surface of the substrate is dried and cured. In the cured coating film formed on the surface of the substrate, ozone decomposition is exhibited by containing the manganese oxide catalyst and activated carbon as coating film components.

[0091] That is, the manganese oxide catalyst adsorbs ozone, reduces the activation energy of the self-decomposition reaction of ozone, and causes the decomposition and desorption reaction of ozone, and the catalytic function of the manganese oxide catalyst reduces and decomposes ozone to convert it into oxygen. In other words, ozone can be reduced to harmless oxygen. Also, activated carbon adsorbs ozone into its pores, and the ozone adsorbed in the activated carbon is converted into carbon monoxide, carbon dioxide (carbon dioxide gas), active oxygen, oxygen, etc. by reacting with the activated carbon or by receiving electrons from the activated carbon (catalytic function that reduces the activation energy of the self-decomposition reaction of ozone). In other words, it can convert ozone into harmless substances. In particular, while manganese dioxide is most active in the high temperature range (for example, around 80°C), activated carbon is highly active in a wide temperature range including room temperature (15 to 25°C) and is also highly active in a high humidity environment.

[0092] In particular, the aqueous coating composition of the present embodiment using the manganese oxide catalyst and activated carbon in combination can obtain a higher ozone decomposition performance than when they are used alone. The reason for this is not entirely clear, but it is considered that, for example, the heat of reaction between activated carbon and ozone promotes the ozone catalytic reaction of the manganese oxide catalyst, the combined use of the manganese oxide catalyst and activated carbon provides ozone decomposition performance in a wide range of temperatures, the manganese oxide catalyst enters the pores of the activated carbon, so that the activated carbon and the manganese oxide catalyst come into contact with ozone efficiently, and the manganese oxide catalyst prevents the oxidation and consumption of the activated carbon by active oxygen, etc., which improves the ozone decomposition ability compared to when only one of the manganese oxide catalyst or activated carbon is used.

[0093] In addition, in order to put it into practical use as a paint, the aqueous paint composition needs to have long-term storage stability, i.e., storage stability. When activated carbon is used alone as a material having ozone decomposition ability, the activated carbon adsorbs and aggregates the resin content (organic matter) of the paint component due to its adsorption characteristics, so it is difficult to ensure the stability of the paint with a specified amount of activated carbon to obtain the desired ozone decomposition performance. However, in the aqueous paint composition of this embodiment, activated carbon and a manganese oxide catalyst are used in combination to decompose ozone, so it is possible to satisfy both ozone decomposition performance and storage stability. In addition, the life of the aqueous paint composition can be extended compared to when activated carbon is used alone. On the other hand, manganese oxide catalysts are expensive, and when only manganese oxide catalysts are used alone, the paint becomes expensive, but activated carbon is available at low cost, so the cost of the aqueous paint composition can be reduced by using a manganese oxide catalyst and activated carbon in combination.

[0094] Thus, according to the aqueous coating composition of the present embodiment containing a manganese oxide catalyst and activated carbon, the cured coating film formed by applying the composition to a substrate and drying contains the manganese oxide catalyst and activated carbon, which makes it possible to decompose ozone in the air that comes into contact with the cured coating film, thereby purifying the air.

[0095] In particular, according to the aqueous coating composition of this embodiment, the aqueous resin that serves as a binder for the manganese oxide catalyst and activated carbon in the cured coating film is one or more of acrylic resin, modified acrylic resin, and fluororesin, so that, as described below, chalking is unlikely to occur even when exposed to light and the composition has high weather resistance.

[0096] Next, examples of the aqueous coating composition according to the embodiment of the present invention will be specifically described. As examples of the aqueous coating composition according to the present embodiment, various aqueous coating compositions were prepared according to the blending compositions shown in Table 1. Reference example, As comparative examples, various water-based coating compositions shown in Table 1 were also prepared.

[0097] [Table 1]

[0098] As shown in Table 1, each example , reference example The water-based paint composition is made of activated carbon (raw material: coconut shell, average particle size: 5 μm, BET specific surface area: 2000 m 2 / g) and a manganese dioxide catalyst (manganese dioxide content: 70% or more, average particle size: 5 μm, BET specific surface area: 250 m 2 / g), a polyacrylate dispersant, water as a solvent, triethylamine (TEA) as a pH adjuster (neutralizer), acrylic resin A (resin solids: 47%, minimum film-forming temperature (MFT): 40°C, glass transition temperature (Tg): 70°C) as a water-based resin, modified acrylic resin A (resin solids: 30%, minimum film-forming temperature: 20°C, glass transition temperature (Tg): 70°C) or fluororesin A (resin solids: 50%, minimum film-forming temperature: 50°C, glass transition temperature (Tg): 50°C) as a water-based resin, and additives (viscosity adjusters and thickening aids). In Table 1, the activated carbon and manganese dioxide catalyst are both 100% solids, and the water is ion-exchanged water added as a solvent. The amount of each material in Table 1 is expressed in parts by mass.

[0099] Each Example , reference example In preparing the aqueous coating composition, first, activated carbon, manganese dioxide catalyst, water as a solvent, and polyacrylate dispersant were mixed according to the formulation in Table 1, and the mixture was placed in a bead mill to carry out a dispersion process. The bead mill used here used 1.5 mm zircon (zirconia bead mill) as media, and dispersed the mixed materials under conditions of a rotation speed of 1500 rpm for 90 minutes.

[0100] Next, a neutralization step was carried out by adding triethylamine (TEA) as a pH adjuster to the mixture dispersed in this manner according to the formulation in Table 1, and then an emulsion of acrylic resin A, modified acrylic resin A, or fluororesin A was mixed into the neutralized mixture according to the formulation in Table 1, and additives (viscosity adjusters and thickening aids) were further added, and the materials were mixed and dispersed by stirring in a disperser for 5 to 10 minutes. Through the above steps, the paint production step was carried out. , reference example Various aqueous coating compositions according to the above were obtained.

[0101] In addition, the present embodiment was produced in this manner. , reference example The water-based paint composition of the present invention has a particle size of particles (activated carbon and manganese dioxide catalyst) that is greater than or equal to the maximum particle diameter (D max ) is 20 μm or less, and the 90% cumulative particle diameter (D 90 ) was less than 10 μm.

[0102] On the other hand, the comparative examples shown in Table 1 are , reference example That is, in the comparative example, polypropylene resin A (resin solid content: 30%, minimum film-forming temperature: 40°C, glass transition temperature (Tg): 30°C), polypropylene resin B (resin solid content: 30%, minimum film-forming temperature: 60°C, glass transition temperature (Tg): 50°C), epoxy resin (resin solid content: 47%, minimum film-forming temperature: 50°C, glass transition temperature (Tg): 60°C), or urethane resin (resin solid content: 47%, minimum film-forming temperature: 10°C, glass transition temperature (Tg): 10°C) was used, and the other materials were the same as those in the examples. , reference example As the same as the example , reference example It was made by the same procedure as

[0103] Here, the examples prepared according to the composition in Table 1 , reference exampleEach of the aqueous coating compositions of the present invention and the comparative examples was applied to a substrate and dried to form a cured coating film (coating film), which was then subjected to evaluation tests for ozone decomposition and weather resistance. In the ozone decomposition test, as shown in Fig. 1, the aqueous coating composition was applied to the surface of a polypropylene substrate 20 (hereinafter referred to as the resin substrate 20) for evaluation, and dried (100°C x 10 minutes) to form a cured coating film 1 (approximately 150mm x 70mm x 10 to 20μm film thickness) on the resin substrate 20 (approximately 150mm x 70mm x 3mm thick), i.e., the test specimen T was used, which is made of a resin substrate 20 with a cured coating film 1 formed from the aqueous coating composition. The aqueous coating composition was applied to the resin substrate 20 until the base material was covered.

[0104] Specifically, as shown in FIG. 1, a test specimen T was placed in a 10 L Tedlar (registered trademark) bag 10 and sealed by heat sealing. Furthermore, air was sealed into the bag from a sleeve S using an air pump (air blower), and then ozone generated by an ozone generator was injected to set the ozone concentration in the bag 10 to 2.0 ppm. After 2 hours, the ozone concentration inside the bag 10 was measured using a detector (ozone sensor) and compared with the initial ozone concentration to calculate the ozone decomposition rate. The evaluation test was carried out at room temperature (normal temperature) of 25°C. When the ozone decomposition rate was 90% or more, it was evaluated as ⊚, when it was 80% or more but less than 90%, it was evaluated as ◯, and when it was less than 80%, it was evaluated as △.

[0105] In the weather resistance test, the aqueous coating composition was applied to the surface of a substrate made of stainless steel (SUS) or aluminum (AL) for evaluation, and then dried (100°C x 10 minutes) to form a cured coating film (approximately 150mm x 70mm x 10 to 20μm film thickness) on the metal substrate (approximately 150mm x 70mm x 1mm thick). In other words, the test specimen was made of a metal substrate with a cured coating film formed from the aqueous coating composition.

[0106] Specifically, a super xenon weather meter (SX75, Suga Test Instruments Co., Ltd.) was used to measure the cumulative irradiation intensity of the evaluation specimen at 250 MJ / m 2 Under the conditions above, a xenon lamp (Super xenon 180W / m 2 Accelerated weather resistance tests were conducted using the super xenon method by irradiating the specimen with ultraviolet light (300 to 400 nm). And the cumulative irradiation intensity is 250MJ / m 2 When the coating surface of the metal substrate of the test specimen, i.e., the cured coating film, was traced with a cloth to check for chalking from the state of powder adhesion to the cloth, and the chalking resistance, i.e., weather resistance, was evaluated. The adhesion of powder to the cloth was rated on a relative four-point scale, with cloth with almost no powder adhesion being rated as ◎, cloth with a small amount of powder adhesion being rated as ◯, cloth with a medium amount of powder adhesion being rated as △, and cloth with a large amount of powder adhesion being judged to have poor weather resistance and not to be practically usable being rated as ×.

[0107] As a comprehensive evaluation, those that received a rating of ◎, ○, or △ in these ozone decomposition and weather resistance evaluation tests were judged to have passed (○), and those that received a rating of × in either the ozone decomposition or weather resistance evaluation test were judged to have failed (×). The results of these evaluation tests are shown in the lower part of Table 1.

[0108] As shown in the lower part of Table 1, the examples are those in which any of acrylic resin, modified acrylic resin, and fluororesin was used as the water-based resin. , reference example In the ozone decomposition test, all of the samples had an ozone decomposition rate of 80% or more and were rated as ◎ or ◯, and in the weather resistance test, all of the samples had a chalking resistance rating of ◎ or ◯, indicating high weather resistance.

[0109] In contrast, in the comparative examples in which polypropylene resin, epoxy resin, or urethane resin was used as the aqueous resin, the ozone decomposition test was rated as ⊚ or ◯, but the weather resistance test was rated as x, and the chalking resistance, i.e., weather resistance, was poor. In particular, these were used at an integrated irradiation intensity of 25 MJ / m 2If the stress exceeds this limit, choking will occur.

[0110] Thus, in the cured coating film of the comparative example formed from an aqueous paint composition using polypropylene resin, epoxy resin or urethane resin, which are commonly used for painting vehicle structural parts such as automobiles, the manganese oxide catalyst is contained, and therefore when exposed to light, the photocatalytic action of the manganese oxide catalyst promotes decomposition of the resin, making the film prone to chalking and poor weather resistance. In contrast, in the cured coating film of the example formed from an aqueous paint composition using either an acrylic resin, modified acrylic resin or fluororesin, resin deterioration is suppressed, making the film less prone to chalking and providing excellent weather resistance.

[0111] The reason for this cannot be determined in one way or another, but for example, acrylic resins, modified acrylic resins, and fluororesins have C—F bonds and OH bonds with high bond energy, and the molecular bond energy and interatomic bond energy of the monomer units that make up the polymer are high, so it is thought that the bonds in the polymer chains are difficult to break even with ultraviolet light or the photocatalytic action of manganese oxide catalysts, making it difficult for the resin (organic matter) to decompose or deteriorate. In other words, the manganese oxide catalyst contained in the coating absorbs the energy of light, becoming in a high-energy state and generating OH radicals and superoxide anions (O2 - It is believed that reactive oxygen species such as hydroxyl radicals and perhydroxyl radicals cut the molecular bond energy of resins (organic substances), causing the resins to decompose and deteriorate. However, acrylic resins, modified acrylic resins, and fluororesins are less likely to decompose or deteriorate because the bond energy between the atoms and molecules that make them up is high. In particular, active oxygen such as OH radicals generated by the photocatalytic action of manganese oxide catalysts is thought to have greater energy than the short wavelengths of ultraviolet light of approximately 300 to 400 nm, such as UVB and UBA, and the deterioration of resins due to this photooxidation catalytic reaction is different from the process of excitation by ultraviolet light and photooxidation deterioration.

[0112] In addition, acrylic resins, modified acrylic resins, and fluororesins have low water absorption and hygroscopicity, which may be related to the fact that hydrolysis of primary bonds and secondary bonds is less likely to occur, the photooxidation catalytic reaction of manganese dioxide catalysts is less likely to proceed, and oxygen is less likely to be transported into the coating film. That is, while manganese oxide catalysts generate hydroxyl radicals and the like through interaction with oxygen and moisture upon absorption of light, acrylic resins, modified acrylic resins, and fluororesins have low water absorption and moisture absorption properties, which reduces the moisture permeability of the coating film and makes it difficult to transport oxygen inside the coating film, which is thought to prevent deterioration due to the photooxidation catalytic reaction of manganese dioxide catalysts.Furthermore, it can be thought that the low water absorption and moisture absorption properties make it difficult to promote autoxidation by light and oxygen. In addition, acrylic resins, modified acrylic resins, and fluororesins have good compatibility and wettability with manganese dioxide-based catalysts, or have low surface energy which reduces the permeability and moisture permeability of water into the coating film, and it can be assumed that these resins can prevent the promotion of photo-oxidation caused by water molecules and can also prevent the promotion of the photo-oxidation catalytic reaction of manganese dioxide-based catalysts.

[0113] Furthermore, it is possible that acrylic resins, modified acrylic resins, and fluororesins have large bond energies such as C-F bonds, OH bonds, C=O bonds, and C=C bonds in the main chain of the polymer, which may suppress the generation of OH radicals themselves in manganese dioxide catalysts. It is also possible that these bonds sterically and electronically protect C-C bonds and C-H bonds, making the structure less susceptible to deterioration. It is also thought that the structural regularity is highly uniform, making them less likely to decompose. In addition, since the temperature rise is relatively small for acrylic resin, modified acrylic resin, and fluororesin, it is also possible to suppress deterioration of the resin and promotion of decomposition reactions due to molecular scission and oxygen bonding caused by heat. In addition, acrylic resins, modified acrylic resins, and fluororesins are generally available with low levels of residual impurities, such as polymerization catalysts used in the polymerization reaction during polymer production and additives that terminate the polymerization reaction, and it is believed that the resins are less susceptible to deterioration due to the action of these residual catalysts.

[0114] In particular, in cured coating films that contain manganese oxide catalysts and activated carbon and have an ozone decomposition effect, it is thought that the oxygen produced by ozone decomposition is one of the factors that makes the resin more susceptible to photo-oxidation deterioration, and it is also thought that H20 produced by the decomposition of organic matter in the photocatalyst is likely to promote the decomposition of resin bonds. However, in this way, in those that use acrylic resin, modified acrylic resin, or fluororesin as a binder, the decomposition and deterioration of these resins is suppressed, making them less susceptible to chalking and providing high weather resistance.

[0115] Here, the inventors prepared aqueous coating compositions using various resins, including acrylic resins, modified acrylic resins, and fluororesins capable of forming cured coating films with high weather resistance, and conducted the same ozone decomposition tests and weather resistance tests as described above.

[0116] First, examples in which various aqueous coating compositions were prepared according to the blending compositions shown in Table 2 using various acrylic resins and varying the total concentration of manganese dioxide catalyst and activated carbon will be described. As shown in Table 2 Reference example 1-1 and Reference example 1-2 is the same as Table 1 above, Reference example 1-3~ Reference example 1-11 were prepared by the same procedure as described above.

[0117] [Table 2]

[0118] As shown in Table 2, Reference example 1-1~ Reference exampleIn each of No. 1-6, acrylic resin A (resin solid content: 47%, minimum film-forming temperature: 40°C, glass transition temperature (Tg): 70°C) was used as the aqueous resin. Reference example 1-1~ Reference example No. 1-6 were prepared by varying the total concentration of manganese dioxide catalyst and activated carbon.

[0119] in particular, Reference example In 1-1, 3.2 g of activated carbon, 7.2 g of manganese dioxide catalyst, and 5.64 g of acrylic resin A in solid content were mixed, and the total amount of manganese dioxide catalyst and activated carbon was 65 parts by mass (rounded to the nearest whole number, the same applies below) per 100 parts by mass of the total amount of acrylic resin A (solid content), activated carbon, and manganese dioxide catalyst. In addition, this Reference example In the formulation of 1-1, the blending amount of acrylic resin A (solid content) is 54 parts by mass per 100 parts by mass of the total amount of manganese dioxide catalyst and activated carbon, and 78 parts by mass per 100 parts by mass of manganese dioxide catalyst. The blending amount of manganese dioxide catalyst is 225 parts by mass per 100 parts by mass of activated carbon, and 45 parts by mass per 100 parts by mass of the total amount of acrylic resin A (solid content), activated carbon, and manganese dioxide catalyst.

[0120] Reference example In 1-2, 2.2 g of activated carbon, 5.1 g of manganese dioxide catalyst, and 17.25 g of acrylic resin A in solid content were blended, and the total blend amount of manganese dioxide catalyst and activated carbon was 30 parts by mass per 100 parts by mass of the total blend amount of acrylic resin A (solid content), activated carbon, and manganese dioxide catalyst. In addition, this Reference exampleIn the formulation of 1-2, the blending amount of acrylic resin A (solid content) is 236 parts by mass per 100 parts by mass of the combined amount of manganese dioxide catalyst and activated carbon, and 338 parts by mass per 100 parts by mass of manganese dioxide catalyst. The blending amount of manganese dioxide catalyst is 232 parts by mass per 100 parts by mass of activated carbon, and 21 parts by mass per 100 parts by mass of the combined amount of acrylic resin A (solid content), activated carbon, and manganese dioxide catalyst.

[0121] Reference example In 1-3, 3.6 g of activated carbon, 8.0 g of manganese dioxide catalyst, and 3.81 g of acrylic resin A in solid content were blended, and the total blend amount of manganese dioxide catalyst and activated carbon was 75 parts by mass per 100 parts by mass of the total blend amount of acrylic resin A (solid content), activated carbon, and manganese dioxide catalyst. In addition, this Reference example In the formulation of 1-3, the blending amount of acrylic resin A (solid content) is 33 parts by mass per 100 parts by mass of the total amount of manganese dioxide catalyst and activated carbon, and 48 parts by mass per 100 parts by mass of manganese dioxide catalyst. The blending amount of manganese dioxide catalyst is 222 parts by mass per 100 parts by mass of activated carbon, and 52 parts by mass per 100 parts by mass of the total amount of acrylic resin A (solid content), activated carbon, and manganese dioxide catalyst.

[0122] Reference example In 1-4, 2.6 g of activated carbon, 5.9 g of manganese dioxide catalyst, and 10.39 g of acrylic resin A in solid content were blended, and the total blend amount of manganese dioxide catalyst and activated carbon was 45 parts by mass per 100 parts by mass of the total blend amount of acrylic resin A (solid content), activated carbon, and manganese dioxide catalyst. In addition, this Reference exampleIn the formulation of 1-4, the blending amount of acrylic resin A (solid content) is 122 parts by mass per 100 parts by mass of the combined amount of manganese dioxide catalyst and activated carbon, and 176 parts by mass per 100 parts by mass of manganese dioxide catalyst. The blending amount of manganese dioxide catalyst is 227 parts by mass per 100 parts by mass of activated carbon, and 31 parts by mass per 100 parts by mass of the combined amount of acrylic resin A (solid content), activated carbon, and manganese dioxide catalyst.

[0123] Reference example In 1-5, 2.3 g of activated carbon, 5.3 g of manganese dioxide catalyst, and 14.15 g of acrylic resin A in solid content were blended, and the total blend amount of manganese dioxide catalyst and activated carbon was 35 parts by mass per 100 parts by mass of the total blend amount of acrylic resin A (solid content), activated carbon, and manganese dioxide catalyst. In addition, this Reference example In the formulation of 1-5, the blending amount of acrylic resin A (solid content) is 186 parts by mass per 100 parts by mass of the combined amount of manganese dioxide catalyst and activated carbon, and 267 parts by mass per 100 parts by mass of manganese dioxide catalyst. The blending amount of manganese dioxide catalyst is 230 parts by mass per 100 parts by mass of activated carbon, and 24 parts by mass per 100 parts by mass of the combined amount of acrylic resin A (solid content), activated carbon, and manganese dioxide catalyst.

[0124] Reference example In 1-6, 2.0 g of activated carbon, 4.7 g of manganese dioxide catalyst, and 20.07 g of acrylic resin A in solid content were blended, and the total blend amount of manganese dioxide catalyst and activated carbon was 75 parts by mass per 100 parts by mass of the total blend amount of acrylic resin A (solid content), activated carbon, and manganese dioxide catalyst. In addition, this Reference exampleIn the formulation of 1-6, the blending amount of acrylic resin A (solid content) is 300 parts by mass per 100 parts by mass of the total amount of manganese dioxide catalyst and activated carbon, and 427 parts by mass per 100 parts by mass of manganese dioxide catalyst. The blending amount of manganese dioxide catalyst is 235 parts by mass per 100 parts by mass of activated carbon, and 18 parts by mass per 100 parts by mass of the total amount of acrylic resin A (solid content), activated carbon, and manganese dioxide catalyst.

[0125] As shown in Table 2, the same acrylic resin A was used, but the total concentration of the manganese dioxide catalyst and activated carbon was varied. Reference example 1-1~ Reference example In 1-6, the lower the total concentration of the manganese dioxide catalyst and activated carbon, the lower the ozone decomposition rate, but the higher the weather resistance (chalking resistance). In other words, the higher the total concentration of the manganese dioxide catalyst and activated carbon, the higher the ozone decomposition rate, but the lower the weather resistance.

[0126] More specifically, the total concentration of manganese dioxide catalyst and activated carbon was set to 75%. Reference example In 1-3, the ozone decomposition rate was 99.9%, and the total concentration of manganese dioxide catalyst and activated carbon was 65%. Reference example In 1-1, the ozone decomposition rate was 99.8%, and the total concentration of manganese dioxide catalyst and activated carbon was 45%. Reference example In 1-4, the ozone decomposition rate was 99.8%, and the total concentration of manganese dioxide catalyst and activated carbon was 35%. Reference example In 1-5, the ozone decomposition rate was 87.2%, and the total concentration of manganese dioxide catalyst and activated carbon was 30%. Reference example In 1-2, the ozone decomposition rate was 80.9%, and the total concentration of manganese dioxide catalyst and activated carbon was 25%. Reference example In 1-2, the ozone decomposition rate was 75.2%.

[0127] If the total concentration of the manganese dioxide catalyst and activated carbon exceeds 75%, the weather resistance decreases, and if the total concentration of the manganese dioxide catalyst and activated carbon is less than 25%, the ozone decomposition property decreases. That is, if the total concentration of the manganese dioxide catalyst and activated carbon is increased, high ozone decomposition property can be obtained, but if the manganese dioxide catalyst and activated carbon are increased and the aqueous resin is decreased, the deterioration of the resin is promoted by the photocatalytic action of the manganese dioxide resin under exposure to sunlight, etc., and chalking is likely to occur. From the viewpoint of high ozone decomposition property, it is preferably 25% or more, more preferably 30% or more, and even more preferably 45% or more. From the viewpoint of high weather resistance, it is preferably 75% or less, more preferably 70% or less, and even more preferably 65% ​​or less. When the total concentration of the manganese dioxide catalyst and activated carbon is preferably within the range of 25% to 75%, it is possible to achieve both ozone decomposition property and weather resistance, more preferably within the range of 30% to 70%, and even more preferably within the range of 30% to 65%.

[0128] Also, Reference example 1-7 and Reference example 1-8 uses acrylic resin B (resin solid content: 47%, minimum film-forming temperature: 100°C, glass transition temperature (Tg): -20°C) as the water-based resin. Reference example 1-7 and Reference example No. 1-8 were prepared by varying the total concentration of the manganese dioxide catalyst and activated carbon.

[0129] in particular, Reference example In 1-7, 3.2 g of activated carbon, 7.2 g of manganese dioxide catalyst, and 5.63 g of acrylic resin B in solid content were blended, so that the total blend amount of manganese dioxide catalyst and activated carbon was 65 parts by mass per 100 parts by mass of the total blend amount of acrylic resin B (solid content), activated carbon, and manganese dioxide catalyst. In addition, this Reference exampleIn the formulation of 1-7, the blending amount of acrylic resin B (solid content) is 54 parts by mass per 100 parts by mass of the combined amount of manganese dioxide catalyst and activated carbon, and 78 parts by mass per 100 parts by mass of manganese dioxide catalyst. The blending amount of manganese dioxide catalyst is 225 parts by mass per 100 parts by mass of activated carbon, and 50 parts by mass per 100 parts by mass of the combined amount of acrylic resin B (solid content), activated carbon, and manganese dioxide catalyst.

[0130] Reference example In 1-8, 2.2 g of activated carbon, 5.1 g of manganese dioxide catalyst, and 19.15 g of acrylic resin A in solid content were blended, and the total blend amount of manganese dioxide catalyst and activated carbon was 30 parts by mass per 100 parts by mass of the total blend amount of acrylic resin B (solid content), activated carbon, and manganese dioxide catalyst. In addition, this Reference example In the formulation of 1-8, the blending amount of acrylic resin B (solid content) is 262 parts by mass per 100 parts by mass of the combined amount of manganese dioxide catalyst and activated carbon, and 376 parts by mass per 100 parts by mass of manganese dioxide catalyst. The blending amount of manganese dioxide catalyst is 232 parts by mass per 100 parts by mass of activated carbon, and 19 parts by mass per 100 parts by mass of the combined amount of acrylic resin B (solid content), activated carbon, and manganese dioxide catalyst.

[0131] Reference example 1-9 and Reference example 1-10 uses acrylic resin C (resin solid content: 50%, minimum film-forming temperature: 60°C, glass transition temperature (Tg): 90°C) as the water-based resin. Reference example 1-9 and Reference example Nos. 1 to 10 were prepared by varying the total concentration of the manganese dioxide catalyst and activated carbon.

[0132] in particular, Reference exampleIn 1-9, 3.2 g of activated carbon, 7.2 g of manganese dioxide catalyst, and 5.65 g of acrylic resin C in solid content were blended, so that the total blend amount of manganese dioxide catalyst and activated carbon was 65 parts by mass per 100 parts by mass of the total blend amount of acrylic resin C (solid content), activated carbon, and manganese dioxide catalyst. In addition, this Reference example In the formulation of 1-9, the blending amount of acrylic resin C (solid content) is 54 parts by mass per 100 parts by mass of the combined amount of manganese dioxide catalyst and activated carbon, and 79 parts by mass per 100 parts by mass of manganese dioxide catalyst. The blending amount of manganese dioxide catalyst is 225 parts by mass per 100 parts by mass of activated carbon, and 50 parts by mass per 100 parts by mass of the combined amount of acrylic resin C (solid content), activated carbon, and manganese dioxide catalyst.

[0133] Reference example In Example 1-10, 2.2 g of activated carbon, 5.1 g of manganese dioxide catalyst, and 17.25 g of acrylic resin C in solid content were blended, and the total blend amount of manganese dioxide catalyst and activated carbon was 30 parts by mass per 100 parts by mass of the total blend amount of acrylic resin C (solid content), activated carbon, and manganese dioxide catalyst. In addition, this Reference example In the formulation of 1-10, the blending amount of acrylic resin C (solid content) is 236 parts by mass per 100 parts by mass of the total amount of manganese dioxide catalyst and activated carbon, and 337 parts by mass per 100 parts by mass of manganese dioxide catalyst. Also, the blending amount of manganese dioxide catalyst is 232 parts by mass per 100 parts by mass of activated carbon, and 21 parts by mass per 100 parts by mass of the total amount of acrylic resin C (solid content), activated carbon, and manganese dioxide catalyst.

[0134] Reference example In No. 1-11, acrylic resin D (resin solid content: 30%, minimum film-forming temperature: 70° C., glass transition temperature (Tg): 120° C.) was used as the aqueous resin. this Reference exampleIn Example 1-11, 2.2 g of activated carbon, 5.1 g of manganese dioxide catalyst, and 17.25 g of acrylic resin C in solid content were blended, and the total blend amount of manganese dioxide catalyst and activated carbon was 30 parts by mass per 100 parts by mass of the total blend amount of acrylic resin D (solid content), activated carbon, and manganese dioxide catalyst. In addition, this Reference example In the formulation of 1-11, the blending amount of acrylic resin D (solid content) is 236 parts by mass per 100 parts by mass of the total amount of manganese dioxide catalyst and activated carbon, and 338 parts by mass per 100 parts by mass of manganese dioxide catalyst. The blending amount of manganese dioxide catalyst is 232 parts by mass per 100 parts by mass of activated carbon, and 21 parts by mass per 100 parts by mass of the total amount of acrylic resin C (solid content), activated carbon, and manganese dioxide catalyst.

[0135] Table 2 Reference example 1-1~ Reference example As shown in 1-11, good weather resistance was obtained regardless of the acrylic resin used, and good weather resistance and ozone decomposition properties were obtained by keeping the total concentration of the manganese dioxide catalyst and activated carbon within the specified range of 25% to 75%.

[0136] Generally, it is believed that the lower the glass transition temperature, the more active the molecular motion at room temperature is, and therefore the more likely the deterioration reaction is to occur. Reference example 1-2, Reference example 1-8, Reference example 1-10, and Reference example As can be seen from the comparison of 1-11, the lower the glass transition temperature (Tg) of the acrylic resin, the higher the weather resistance. The reason for this is not entirely clear, but it is thought that acrylic resins with a low glass transition temperature (Tg) have a large number of carbon atoms in the side chain, which requires a lot of energy to dissociate.

[0137] According to the experimental research of the present inventors, acrylic resins can obtain good weather resistance if they have a glass transition temperature of 130° C. or lower, more preferably 120° C. or lower, even more preferably 90° C. or lower, and particularly preferably 70° C. or lower. On the other hand, those with too low a glass transition temperature have reduced heat resistance and are not suitable for use under high temperature environmental conditions, so that those with a glass transition temperature of -30° C. or higher are preferable, those with a glass transition temperature of -25° C. or higher are more preferable, and those with a glass transition temperature of -20° C. or higher are even more preferable.

[0138] Next, examples in which various water-based paint compositions were prepared using various modified acrylic resins according to the blending compositions shown in Table 3 will be described. Examples 2-1 and 2-2 shown in Table 3 are the same as those in Table 1 above, and Examples 2-3 and 2-4 were prepared by the same procedure as described above.

[0139] [Table 3]

[0140] As described above, in Examples 2-1 and 2-2, modified acrylic resin A (resin solid content: 30%, minimum film-forming temperature: 20°C, glass transition temperature (Tg): 70°C) was used as the aqueous resin. In Example 2-3, modified acrylic resin B (resin solid content: 30%, minimum film-forming temperature: 50° C., glass transition temperature (Tg): 80° C.) was used as the aqueous resin. In Example 2-4, modified acrylic resin C (resin solid content: 45%, minimum film-forming temperature: 70° C., glass transition temperature (Tg): 110° C.) was used as the aqueous resin.

[0141] Specifically, in Example 2-1, 3.2 g of activated carbon, 7.2 g of manganese dioxide catalyst, and 5.58 g of modified acrylic resin A in solid content were blended, so that the total blend amount of manganese dioxide catalyst and activated carbon was 65 parts by mass per 100 parts by mass of the total blend amount of modified acrylic resin A (solid content), activated carbon, and manganese dioxide catalyst. In the formulation of Example 2-1, the amount of modified acrylic resin A (solid content) was 54 parts by mass per 100 parts by mass of the total amount of manganese dioxide catalyst and activated carbon, and 78 parts by mass per 100 parts by mass of manganese dioxide catalyst. The amount of manganese dioxide catalyst was 225 parts by mass per 100 parts by mass of activated carbon, and 45 parts by mass per 100 parts by mass of the total amount of modified acrylic resin A (solid content), activated carbon, and manganese dioxide catalyst.

[0142] In Example 2-2, 2.2 g of activated carbon, 5.1 g of manganese dioxide catalyst, and 17.25 g of modified acrylic resin A in solid content were blended, and the total blend amount of manganese dioxide catalyst and activated carbon was 30 parts by mass per 100 parts by mass of the total blend amount of modified acrylic resin A (solid content), activated carbon, and manganese dioxide catalyst. In the formulation of Example 2-2, the amount of modified acrylic resin A (solid content) was 236 parts by mass per 100 parts by mass of the total amount of manganese dioxide catalyst and activated carbon, and 338 parts by mass per 100 parts by mass of manganese dioxide catalyst. The amount of manganese dioxide catalyst was 232 parts by mass per 100 parts by mass of activated carbon, and 21 parts by mass per 100 parts by mass of the total amount of modified acrylic resin A (solid content), activated carbon, and manganese dioxide catalyst.

[0143] In Example 2-3, 2.2 g of activated carbon, 5.1 g of manganese dioxide catalyst, and 17.25 g of modified acrylic resin B in solid content were blended, so that the total blend amount of manganese dioxide catalyst and activated carbon was 65 parts by mass per 100 parts by mass of the total blend amount of modified acrylic resin B (solid content), activated carbon, and manganese dioxide catalyst. In the formulation of Example 2-3, the amount of modified acrylic resin B (solid content) was 236 parts by mass per 100 parts by mass of the total amount of manganese dioxide catalyst and activated carbon, and 338 parts by mass per 100 parts by mass of manganese dioxide catalyst. The amount of manganese dioxide catalyst was 232 parts by mass per 100 parts by mass of activated carbon, and 21 parts by mass per 100 parts by mass of the total amount of modified acrylic resin B (solid content), activated carbon, and manganese dioxide catalyst.

[0144] In Example 2-4, 2.2 g of activated carbon, 5.1 g of manganese dioxide catalyst, and 17.25 g of modified acrylic resin C in solid content were blended, and the total blend amount of manganese dioxide catalyst and activated carbon was 30 parts by mass per 100 parts by mass of the total blend amount of modified acrylic resin C (solid content), activated carbon, and manganese dioxide catalyst. In the formulation of Example 2-4, the amount of modified acrylic resin C (solid content) was 236 parts by mass per 100 parts by mass of the total amount of manganese dioxide catalyst and activated carbon, and 338 parts by mass per 100 parts by mass of manganese dioxide catalyst. The amount of manganese dioxide catalyst was 232 parts by mass per 100 parts by mass of activated carbon, and 21 parts by mass per 100 parts by mass of the total amount of modified acrylic resin C (solid content), activated carbon, and manganese dioxide catalyst.

[0145] As shown in Examples 2-1 to 2-4, good weather resistance was obtained with any of the modified acrylic resins, and good ozone decomposition properties were obtained when the total concentration of the manganese dioxide catalyst and activated carbon was in the range of 30% to 65%. In particular, as can be seen from the comparison of Examples 2-2, 2-3, and 2-4, modified acrylic resins with low glass transition temperatures (Tg) also have high weather resistance. According to the experimental research of the present inventors, modified acrylic resins with a glass transition temperature of 130° C. or lower have good weather resistance, more preferably 110° C. or lower, even more preferably 80° C. or lower, and particularly preferably 70° C. or lower. On the other hand, those with too low a glass transition temperature have reduced heat resistance and are not suitable for use under high temperature environmental conditions, so that the glass transition temperature is preferably -30° C. or higher, more preferably -25° C. or higher, and even more preferably -20° C. or higher.

[0146] Furthermore, examples in which various aqueous coating compositions were prepared using various fluororesins according to the blending compositions shown in Table 4 will be described. Examples 3-1 and 3-2 shown in Table 4 are the same as those in Table 1 above, and Examples 3-3 and 3-4 were prepared by the same procedure as described above.

[0147] [Table 4]

[0148] As described above, in Examples 3-1 and 3-2, fluororesin A (resin solid content: 50%, minimum film-forming temperature: 50° C., glass transition temperature (Tg): 50° C.) was used as the aqueous resin. In Example 3-2, fluororesin B (resin solid content: 50%, minimum film-forming temperature: 70° C., glass transition temperature (Tg): 80° C.) was used as the aqueous resin. In Example 3-3, fluororesin C (resin solid content: 45%, minimum film-forming temperature: 70° C., glass transition temperature (Tg): 90° C.) was used as the aqueous resin.

[0149] Specifically, in Example 3-1, 3.2 g of activated carbon, 7.2 g of manganese dioxide catalyst, and 5.58 g of fluororesin A in solid content were blended, so that the total blend amount of manganese dioxide catalyst and activated carbon was 65 parts by mass per 100 parts by mass of the total blend amount of fluororesin A (solid content), activated carbon, and manganese dioxide catalyst. In the formulation of Example 3-1, the amount of fluororesin A (solid content) was 54 parts by mass per 100 parts by mass of the total amount of manganese dioxide catalyst and activated carbon, and 78 parts by mass per 100 parts by mass of manganese dioxide catalyst. The amount of manganese dioxide catalyst was 225 parts by mass per 100 parts by mass of activated carbon, and 45 parts by mass per 100 parts by mass of the total amount of fluororesin A (solid content), activated carbon, and manganese dioxide catalyst.

[0150] In Example 3-2, 2.2 g of activated carbon, 5.1 g of manganese dioxide catalyst, and 17.25 g of fluororesin A in solid content were blended, so that the total blend amount of manganese dioxide catalyst and activated carbon was 30 parts by mass per 100 parts by mass of the total blend amount of fluororesin A (solid content), activated carbon, and manganese dioxide catalyst. In the blend of Example 3-2, the blending amount of fluororesin A (solid content) was 236 parts by mass per 100 parts by mass of the total amount of manganese dioxide catalyst and activated carbon, and 338 parts by mass per 100 parts by mass of manganese dioxide catalyst. The blending amount of manganese dioxide catalyst was 232 parts by mass per 100 parts by mass of activated carbon, and 21 parts by mass per 100 parts by mass of the total amount of fluororesin A (solid content), activated carbon, and manganese dioxide catalyst.

[0151] In Example 3-3, 2.2 g of activated carbon, 5.1 g of manganese dioxide catalyst, and 17.25 g of fluororesin B in solid content were blended, so that the total blend amount of manganese dioxide catalyst and activated carbon was 65 parts by mass per 100 parts by mass of the total blend amount of fluororesin B (solid content), activated carbon, and manganese dioxide catalyst. In the formulation of Example 3-3, the amount of fluororesin B (solid content) was 236 parts by mass per 100 parts by mass of the total amount of manganese dioxide catalyst and activated carbon, and 338 parts by mass per 100 parts by mass of manganese dioxide catalyst. The amount of manganese dioxide catalyst was 232 parts by mass per 100 parts by mass of activated carbon, and 21 parts by mass per 100 parts by mass of the total amount of fluororesin B (solid content), activated carbon, and manganese dioxide catalyst.

[0152] In Example 3-4, 2.2 g of activated carbon, 5.1 g of manganese dioxide catalyst, and 17.24 g of fluororesin C in solid content were blended, and the total blend amount of manganese dioxide catalyst and activated carbon was 30 parts by mass per 100 parts by mass of the total blend amount of fluororesin C (solid content), activated carbon, and manganese dioxide catalyst. In the formulation of Example 3-4, the amount of fluororesin C (solid content) was 236 parts by mass per 100 parts by mass of the total amount of manganese dioxide catalyst and activated carbon, and 338 parts by mass per 100 parts by mass of manganese dioxide catalyst. The amount of manganese oxide catalyst was 232 parts by mass per 100 parts by mass of activated carbon, and 21 parts by mass per 100 parts by mass of the total amount of fluororesin C (solid content), activated carbon, and manganese dioxide catalyst.

[0153] As shown in Examples 3-1 to 3-4, good weather resistance was obtained with any of the fluororesins, and good ozone decomposition properties were obtained when the total concentration of the manganese dioxide catalyst and activated carbon was in the range of 30% to 65%. In particular, as can be seen from a comparison of Examples 3-2, 3-3, and 3-4, fluororesins with a lower glass transition temperature (Tg) also have higher weather resistance. According to the experimental research of the present inventors, fluororesins with a glass transition temperature of 100° C. or lower have good weather resistance, more preferably 90° C. or lower, even more preferably 80° C. or lower, and particularly preferably 50° C. or lower. On the other hand, fluororesins with too low a glass transition temperature have reduced heat resistance and are not suitable for use under high temperature environmental conditions, so that a glass transition temperature of -30° C. or higher is preferable, more preferably -25° C. or higher, and even more preferably -20° C. or higher.

[0154] In all of the above examples, the inventors stored the prepared aqueous coating compositions for one month at a temperature of 20° C. and checked for the presence or absence of aggregation after one month, confirming that no aggregation occurred even after storage at 20° C. for one month, demonstrating excellent storage stability. Furthermore, regardless of whether the substrate was metallic or made of resin (non-metallic), the cured coating films prepared in the above examples also had good adhesion to those substrates.

[0155] Meanwhile, the present inventors further investigated the optimum blending of one or more aqueous resins selected from acrylic resin, modified acrylic resin, and fluororesin, which are coating film components, and the manganese oxide catalyst and activated carbon that exhibit ozone decomposition properties, and found that the blending amount of one or more aqueous resins selected from acrylic resin, modified acrylic resin, and fluororesin is preferably within the range of 20 to 400 parts by mass per 100 parts by mass of the total amount (solid content) of the manganese oxide catalyst and activated carbon, more preferably within the range of 25 to 350 parts by mass, even more preferably within the range of 30 to 300 parts by mass, and particularly preferably within the range of 50 to 280 parts by mass. When the amount of the aqueous resin, which is one or more of acrylic resin, modified acrylic resin, and fluororesin, mixed with the manganese oxide catalyst and activated carbon is too large, the amount of the ozone decomposable manganese oxide catalyst and activated carbon is relatively low, and the ozone decomposability is reduced. Therefore, the amount of the aqueous resin is preferably 400 parts by mass or less, more preferably 350 parts by mass or less, even more preferably 300 parts by mass or less, and particularly preferably 280 parts by mass or less, relative to 100 parts by mass of the total amount of the manganese oxide catalyst and activated carbon. On the other hand, when the amount of the aqueous resin is too large with respect to the manganese oxide catalyst and activated carbon, the amount of the aqueous resin as a binder is relatively low, and the composition is brittle and deteriorates quickly, and the chalking resistance is reduced. Therefore, the amount of the aqueous resin is preferably 20 parts by mass or more, more preferably 25 parts by mass or more, even more preferably 30 parts by mass or more, and particularly preferably 50 parts by mass or more, relative to 100 parts by mass of the total amount of the manganese oxide catalyst and activated carbon. Within the above range, both ozone decomposition property and chalking resistance, i.e., weather resistance, can be achieved.

[0156] Furthermore, the blending amount of one or more aqueous resins selected from acrylic resins, modified acrylic resins, and fluororesins is preferably within a range of 30 to 500 parts by mass, more preferably 40 to 480 parts by mass, even more preferably 45 to 450 parts by mass, and particularly preferably 70 to 400 parts by mass, relative to 100 parts by mass of the manganese oxide catalyst. If the amount of the aqueous resin, which is one or more of acrylic resin, modified acrylic resin, and fluororesin, mixed with the manganese oxide catalyst is too large, the amount of the ozone-decomposing manganese oxide catalyst is relatively low, and the ozone decomposing performance due to the synergistic effect of the manganese oxide catalyst and the activated carbon is reduced. Therefore, the amount of the aqueous resin is preferably 500 parts by mass or less, more preferably 480 parts by mass or less, even more preferably 450 parts by mass or less, and particularly preferably 400 parts by mass or less, relative to 100 parts by mass of the manganese oxide catalyst. On the other hand, if the amount of the aqueous resin is too large relative to the manganese oxide catalyst, the concentration of the aqueous resin as a binder is relatively low and the concentration of the manganese oxide catalyst is relatively high, and the chalking resistance is reduced. Therefore, the amount of the aqueous resin is preferably 30 parts by mass or more, more preferably 40 parts by mass or more, even more preferably 45 parts by mass or more, and particularly preferably 70 parts by mass or more, relative to 100 parts by mass of the manganese oxide catalyst. Within the above range, it is possible to improve both ozone decomposition property and chalking resistance, that is, weather resistance.

[0157] Furthermore, the manganese oxide catalyst is preferably blended in a range of 11 to 900 parts by mass, more preferably 15 to 800 parts by mass, and even more preferably 20 to 700 parts by mass, per 100 parts by mass of activated carbon. If the amount of the manganese oxide catalyst is too large relative to the amount of activated carbon, the weather resistance is reduced. In addition, the cost is increased. Therefore, the amount of the manganese oxide catalyst is preferably 900 parts by mass or less, more preferably 800 parts by mass or less, and even more preferably 700 parts by mass or less, relative to 100 parts by mass of activated carbon. On the other hand, if the amount of the manganese oxide catalyst is small and the amount of activated carbon is relatively large, the activated carbon is likely to aggregate, which reduces dispersibility and coatability. Therefore, the amount of the manganese oxide catalyst is preferably 11 parts by mass or more, more preferably 15 parts by mass or more, and even more preferably 20 parts by mass or more, relative to 100 parts by mass of activated carbon. Within the above range, both coatability and weather resistance can be achieved, and low cost can be achieved.

[0158] In addition, the manganese oxide catalyst is preferably blended in an amount within a range of 5 to 65 parts by mass relative to 100 parts by mass of the total amount of the manganese oxide catalyst, activated carbon, and aqueous resin, more preferably 10 to 60 parts by mass, even more preferably 15 to 55 parts by mass, and particularly preferably 18 to 50 parts by mass. If the concentration of the manganese oxide catalyst, which is a coating component, is too high, the weather resistance decreases. Therefore, the manganese oxide catalyst is preferably 65 parts by mass or less, more preferably 60 parts by mass or less, even more preferably 55 parts by mass or less, and even more preferably 50 parts by mass or less, relative to 100 parts by mass of the total amount of the manganese oxide catalyst, activated carbon, and aqueous resin. On the other hand, if the concentration of the manganese oxide catalyst is too low, the ozone decomposition property due to the synergistic effect of the manganese oxide catalyst and activated carbon will decrease. Therefore, the manganese oxide catalyst is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, even more preferably 15 parts by mass or more, and even more preferably 18 parts by mass or more, relative to 100 parts by mass of the total amount of the manganese oxide catalyst, activated carbon, and aqueous resin. Within the above range, it is possible to improve both ozone decomposition property and weather resistance.

[0159] Based on the entire aqueous coating composition, the activated carbon is preferably in the range of 1 to 40 mass%, more preferably 1.5 to 20 mass%, even more preferably 2 to 10 mass%, and particularly preferably 2 to 5 mass%, the manganese dioxide catalyst is preferably in the range of 1 to 40 mass%, more preferably 2 to 20 mass%, even more preferably 3 to 15 mass%, and particularly preferably 4 to 10 mass%, and the dispersant is preferably 0.2 to 2 mass%, more preferably 0.3 to 1 mass%, and even more preferably 0.3 to 0. The concentration of the aqueous resin, which is either an acrylic resin, a modified acrylic resin or a fluororesin, is preferably within the range of 2 to 30 mass%, more preferably 2 to 25 mass%, and even more preferably 3 to 25 mass%, calculated on a solid content basis; the pH adjuster is preferably within the range of 0.1 to 5 mass%, more preferably 0.5 to 4 mass%, and even more preferably 1 to 3 mass%; and the additive is at a concentration within the range of 0 to 10 mass%, more preferably 1 to 8 mass%, and even more preferably 3 to 8 mass%.

[0160] In terms of the coating film components of the cured coating film, the activated carbon is preferably in the range of 3 to 60 mass%, more preferably 4 to 35 mass%, even more preferably 5 to 30 mass%, and particularly preferably 5 to 25 mass%, the manganese dioxide-based catalyst is preferably in the range of 3 to 60 mass%, more preferably 5 to 60 mass%, even more preferably 10 to 60 mass%, and particularly preferably 15 to 50 mass%, and the aqueous resin of one or more types of acrylic resin, modified acrylic resin, and fluororesin is preferably in the range of 15 to 90 mass%, more preferably 25 to 85 mass%, and even more preferably 25 to 85 mass%, calculated as solid content.

[0161] In this way, in a cured coating film formed by applying to a substrate an aqueous coating composition containing a manganese oxide catalyst, activated carbon, one or more aqueous resins selected from acrylic resin, modified acrylic resin, and fluororesin, and a dispersant, and having water as the main solvent, and drying the composition, the acrylic resin, modified acrylic resin, or fluororesin is not easily decomposed or deteriorated even by the photocatalytic action of the manganese oxide catalyst when exposed to light, so that the manganese oxide catalyst is not easily peeled off from the resin and the coating film interface is not easily chalked (whitened), and interlayer delamination is also prevented.

[0162] In particular, the relatively large amount of oxygen produced by the decomposition of ozone is thought to create an environment in which photo-oxidation is easily promoted. In addition, manganese oxide catalysts such as manganese dioxide catalysts absorb light and interact with oxygen and moisture to produce hydroxyl radicals and superoxide anions (O2 - ) and perhydroxy radicals, it is thought that the environment is prone to accelerated decomposition of the resin due to the photocatalytic action of the manganese oxide catalyst. However, by using acrylic resin, modified acrylic resin or fluororesin as a binder, the coating film is less likely to chalk (turn white) even when exposed to light due to the photocatalytic action of the manganese oxide catalyst, and it has high weather resistance.

[0163] Deterioration of the coating components may also be affected by the components of the substrate to which the aqueous paint composition is applied. However, the inventors have confirmed through experimental research that the cured coating film formed by applying the aqueous paint composition of this embodiment to a substrate and drying it has good weather resistance, whether the substrate to be painted is made of metal or non-metal, for example, resin.

[0164] Thus, according to the aqueous coating composition of this embodiment, even if it contains a manganese dioxide catalyst having photocatalytic action, the use of acrylic resin, modified acrylic resin, or fluororesin as the aqueous resin gives it high chalking resistance, i.e., weather resistance, so that even when applied to areas exposed to sunlight or other light, chalking is unlikely to occur and it has good durability, making it possible to expand the range of application of the coating.

[0165] As an example of applying the aqueous coating composition of this embodiment, in the case of a vehicle such as an automobile, the aqueous coating composition of this embodiment is applied to a location where there is a lot of air flow when the vehicle is running, for example, the radiator of the vehicle through which the air taken into the engine room passes, the electric fan nearby, the grille, the grille shutter, the undercover, etc., and a cured coating film is formed there, where a lot of air passes through when the vehicle is running, and the ozone remaining in the air in contact with the cured coating film can be effectively decomposed, removed, and reduced. That is, the ozone in the atmosphere can be effectively purified while the vehicle is running, and harmful substances in the environment can be reduced.

[0166] For example, referring to FIG. 2, when an automobile is traveling, if a grill shutter G, which is arranged between an air conditioner condenser (not shown) and a front grill (radiator grill) and can be opened and closed, is in an open state, outside air is taken in through the opening of the front grill of the vehicle. Then, the air (traveling wind) that has passed through the front grill passes through the opening of the grill shutter G, the radiator R that cools the engine, and the fan F1 behind it, and flows into the engine room that houses the engine. Even when the vehicle is stopped, the fan F1, which is attached to the rear of the radiator R and is used to increase the cooling efficiency of the cooling water flowing into the radiator R, rotates forward, and an air flow flows from the front side to the radiator R side due to the suction of the fan F1, and outside air is taken in through the opening of the front grill, passes through the radiator R and the fan F1 behind it, and flows into the engine room side. When the grill shutter G is closed, the air from the outside comes into contact with the grill shutter G, blocking the inflow of air into the radiator R side.

[0167] Thus, by applying the aqueous coating composition of this embodiment to the surfaces of the grille and grill shutter G, which are arranged in the flow path of the airflow generated when the vehicle is running or the fan F1 is rotating and which come into contact with and flow through, the core of the radiator R, the surfaces of the blades of the fan F1, and the like, and drying them to form a cured coating film, the ozone in the air that comes into contact with the cured coating film can be decomposed by the activated carbon and manganese oxide catalyst contained in the cured coating film, thereby making it possible to effectively purify the air. In particular, the blades of the fan F1 are formed in a plate shape, and the components of the grille and grill shutter G are also formed in a mesh or lattice shape with wide openings, so that the paint can be easily coated on the surfaces of the components by a simple coating technique such as spraying the aqueous coating composition.

[0168] In particular, exterior parts of such automobiles, including the grille, grill shutter G, radiator R and electric fan F1 located nearby, are exposed to sunlight and other light, so a cured coating film formed from the aqueous paint composition of this embodiment has chalking resistance, i.e., weather resistance, and is therefore less likely to fall off over long periods of time, and the extended life of the coating makes it possible to maintain ozone decomposition properties for a long period of time.

[0169] In addition, the aqueous coating composition of the present embodiment can be applied to not only vehicle parts such as automobiles, but also to fans (including bladeless fans), circulators, air conditioners, air purifiers, and other fans that generate airflow, and since these generate airflow, the ozone in the atmosphere can be decomposed by the manganese dioxide catalyst and activated carbon in the cured coating film formed from the aqueous coating composition, thereby effectively purifying the ozone in the atmosphere, and it is possible to blow air with a reduced ozone concentration. In particular, the cured coating film formed from the aqueous coating composition of the present embodiment has high weather resistance, so that it is difficult to cause chalking and has high durability, making it difficult to detach for a long period of time, and it is possible to maintain ozone decomposition for a long period of time, and it is also suitable for application to parts exposed to sunlight outdoors.

[0170] For example, referring to FIG. 3, if a blower includes a fan F2 having rotating blades that suck in air by driving a motor or the like and blows out (discharges) it, a ventilation member (filter) V arranged in front (blow side or intake side) and behind (intake side or blow side) the fan F2, a cylindrical housing member C that houses the fan F2 and has the ventilation member V arranged in front and behind the fan F2 attached to its end, and a drive unit (not shown) such as a motor that rotates and drives the fan F2, the aqueous coating composition of this embodiment is applied to the fan F2, the ventilation member V, and the housing member C, in particular, for example, the blades of the fan F2, the entire or partial surface of the member constituting the ventilation member V, and the inner peripheral surface of the housing member C, and then dried to form a cured coating film, the ozone in the air that comes into contact with the cured coating film can be decomposed by the activated carbon and manganese oxide catalyst contained in the cured coating film, thereby making it possible to effectively purify the air.

[0171] The fan F2 draws in and blows out air by rotational drive, and can be, for example, an axial flow fan (propeller fan), a centrifugal fan (sirocco fan, turbo fan), a diagonal flow fan (mixed flow fan), a transverse flow fan (cross flow fan, cross-flow fan, line flow fan (registered trademark)), etc. The ventilation member V is installed in the flow path of the airflow generated by the fan F2, and the shape is not particularly limited as long as it allows air to flow. For example, it may be in the form of a plurality of rings arranged concentrically as shown in FIG. 3, a mesh shape, a honeycomb shape, a fence shape, a lattice shape, a vane shape (a plurality of straight or curved shapes arranged radially or spirally from the center), a plurality of through holes having a circular or polygonal cross-sectional shape (triangular, rectangular, etc.), or the like, and the through holes and gaps between the members that allow air to flow are formed. For example, a honeycomb shape or a shape with unevenness can increase the contact area with air and increase the coating area, thereby enhancing the ozone reduction effect. In particular, a honeycomb shape can reduce pressure loss. The accommodating member C is cylindrical with a diameter larger than the outer diameter of the fan F2, accommodates the fan F2, and guides the air drawn in by the rotational drive of the fan F2 to the blowing side (exhaust side), thereby increasing the air flow rate of the fan F2. The blower which houses the fan F2 and has the ventilation member V attached thereto may be one which is supported by a supporting member such as a tripod or a base and thereby installed on the floor or the ground, or it may be one which is suspended and may be any of a floor-standing type (ground-standing type), a table-top type, a ceiling-mounted type, a side wall-mounted type, etc.

[0172] When the aqueous coating composition of the present embodiment is applied to such a blower, the aqueous coating composition containing a manganese oxide catalyst, activated carbon, one or more aqueous resins selected from acrylic resin, modified acrylic resin and fluororesin, and a dispersant, and having water as the main solvent, is applied to fan F2, which draws in air and blows it out to generate an air flow, and then dried, resulting in the blower having a cured coating film formed thereon, which contains the manganese oxide catalyst, activated carbon, and one or more aqueous resins selected from acrylic resin, modified acrylic resin and fluororesin. That is, the blower is provided with a fan F2 that draws in air and blows it to generate an air flow, and an aqueous paint composition containing a manganese oxide catalyst, activated carbon, one or more aqueous resins selected from acrylic resin, modified acrylic resin, and fluororesin, and a dispersant, and having water as the main component of the solvent, is applied to the fan F2 and dried to form a cured coating film containing the manganese oxide catalyst, activated carbon, and one or more aqueous resins selected from acrylic resin, modified acrylic resin, and fluororesin.

[0173] In addition, since the blower has a ventilation member V through which the air flow generated by the fan F2 passes, an aqueous coating composition containing a manganese oxide catalyst, activated carbon, one or more aqueous resins selected from acrylic resin, modified acrylic resin, and fluororesin, and a dispersant, and containing water as a main component of a solvent, is applied to the ventilation member V and dried, whereby a cured coating film containing a manganese oxide catalyst, activated carbon, and one or more aqueous resins selected from acrylic resin, modified acrylic resin, and fluororesin is formed on the ventilation member V. In particular, since the ventilation member V such as such a filter has a large contact area with the air, by forming a cured coating film containing activated carbon and a manganese oxide catalyst thereon, the ozone concentration of the air passing therethrough can be effectively reduced. That is, the blower is provided with: a fan F2 that draws in air and blows it to generate an air flow; a ventilation member V through which the air flow generated by the fan F2 passes; and a cured coating film containing a manganese oxide catalyst, activated carbon, one or more water-based resins selected from acrylic resin, modified acrylic resin, and fluororesin, and an aqueous paint composition containing a dispersant and water as the main component of the solvent, and formed on the fan F2 by drying the aqueous paint composition. The cured coating film contains a manganese oxide catalyst, activated carbon, and one or more water-based resins selected from acrylic resin, modified acrylic resin, and fluororesin.

[0174] Furthermore, the blower has a housing member C that houses the fan F2, and by applying to the housing member C an aqueous paint composition that contains a manganese oxide catalyst, activated carbon, one or more aqueous resins selected from acrylic resin, modified acrylic resin and fluororesin, and a dispersant, and has water as the main component of the solvent, and then drying, a cured coating film containing the manganese oxide catalyst, activated carbon, and one or more aqueous resins selected from acrylic resin, modified acrylic resin and fluororesin can be formed on the housing member C. That is, the blower is provided with a fan F2 that draws in air and blows it out to generate an air flow, a ventilation member V through which the air flow generated by the fan F2 passes, a housing member C that houses the fan F2, and a cured coating film that contains a manganese oxide catalyst, activated carbon, and one or more water-based resins selected from acrylic resin, modified acrylic resin, and fluororesin, and an aqueous paint composition that contains a manganese oxide catalyst, activated carbon, and one or more water-based resins selected from acrylic resin, modified acrylic resin, and fluororesin, and a dispersant, and has water as the main component of the solvent, formed on the fan F2 by drying the aqueous paint composition.

[0175] In this way, by applying the aqueous coating composition of the present embodiment to areas where air flows and the air comes into contact with and passes through, and then drying to form a cured coating film and coat it, the manganese dioxide catalyst and activated carbon contained therein can decompose the ozone contained in the air flow, and air with a reduced ozone concentration can be blown out, making it possible to effectively purify ozone in the atmosphere.

[0176] In particular, ozone also has an adverse effect on agricultural and horticultural crops, causing damage to the plants themselves and resulting in reduced growth and yields of agricultural and horticultural crops, but in air conditioning for growing such agricultural and horticultural crops, the use of a blower equipped with a cured coating film containing the above-mentioned manganese oxide catalyst, activated carbon, and one or more aqueous resins selected from acrylic resin, modified acrylic resin, and fluororesin makes it possible to reduce the ozone concentration in the space in which agricultural and horticultural crops are grown, thereby making it possible to reduce damage caused by ozone to agricultural and horticultural crops. That is, an air conditioning system having a blower equipped with a cured coating film containing a manganese oxide catalyst, activated carbon, and one or more aqueous resins selected from acrylic resin, modified acrylic resin, and fluororesin makes it possible to reduce the ozone concentration in the air environment, and provides a space with a reduced ozone concentration.

[0177] Of course, the present invention can also contribute to reducing the ozone concentration in the atmosphere and air by applying the same to fans in home and factory air conditioning equipment, or to other items, such as railway cars, ships, aircraft, building structures, construction equipment, office automation equipment that generates ozone, electrical equipment (e.g., dry copy machines, ozonizers, ultraviolet lamps, air purifiers (for deodorization, sterilization, bleaching, etc.)), such as housings for purification devices, casings near ozone generators (high-voltage generators, corona chargers, etc.), exhaust filters, exhaust ducts, exhaust fans, etc. For example, in a room where an air purifier that uses ozone to disinfect and deodorize viruses and the like is used, particularly in a space where medical instruments and the like are disinfected, there is an unpleasant odor due to residual ozone. In order to decompose such residual ozone, the aqueous coating composition of this embodiment can be applied to the walls of the room or the blower of an air conditioning system, and the manganese oxide catalyst and activated carbon contained in the coating film formed from the composition can decompose the remaining ozone remaining in the room, thereby improving the working environment.

[0178] In this way, the surface of a portion (such as a structure) that comes into contact with the atmosphere or air is covered with the aqueous coating composition of this embodiment, and ozone decomposition performance is imparted by surface treatment (painting) to form a cured coating film on the surface, and by applying the aqueous coating composition of this embodiment to a portion that comes into contact with the atmosphere or air, it becomes possible to reduce ozone remaining in the atmosphere. The aqueous coating composition of this embodiment is a paint made by finely dispersing a manganese oxide catalyst and activated carbon, and since it is a paint to be applied to a substrate, it is easy to work with and can be applied to a wide range of items and parts, and can effectively contribute to air purification. In particular, since the cured coating film formed from the aqueous coating composition of this embodiment has high weather resistance, even when applied to articles used indoors or outdoors, i.e., when applied to articles (including structures and parts) used in places exposed to sunlight or other light, exterior walls, exterior materials, exterior parts, etc., chalking is unlikely to occur and the coating film has high durability, making it possible to extend the life of the coating film and maintain a high ozone decomposition effect for a long period of time.

[0179] Incidentally, an article formed by applying the aqueous coating composition of this embodiment to a substrate in this manner can be considered to be a coated article (coated article, painted article) comprising the substrate (object to be coated, coated material) and a cured coating film containing a manganese oxide catalyst, activated carbon, one or more aqueous resins selected from acrylic resin, modified acrylic resin and fluororesin, and a dispersant, which is formed on the surface of the substrate by applying an aqueous coating composition having water as the main solvent component to the substrate and drying the aqueous coating composition. The cured coating film contains a manganese oxide catalyst, activated carbon, and one or more aqueous resins selected from acrylic resin, modified acrylic resin and fluororesin.

[0180] Here, the substrate may be an article that comes into contact with air, or preferably an article through which an air flow passes, such as a grille, grill shutter, radiator, or radiator fan of a vehicle such as an automobile, or a filter (fiber filter, nonwoven fabric filter, metal filter, ceramic filter, resin filter, HPA filter (High Efficiency Particulate Air Filter), ULPA filter (Ultra Low Penetration Air Filter)) used in air conditioning equipment, blowers, air conditioners, air purifiers, copiers, printers, etc. These include air conditioners, air circulators, air conditioners (including outdoor units), air purifiers (including air purifiers that use ozone to disinfect and deodorize viruses, etc.), fans used in ventilation fans, ducts made of metal or resin used in air conditioning systems (air supply ducts, exhaust ducts, air circulation ducts, etc.), building materials (interior and exterior materials, wall materials, roofing materials, flooring materials, ceiling materials, screen doors, windows, curtains, fences), agricultural and horticultural materials (vinyl sheets for vinyl greenhouses, sheets, nets and mulch for weeding, pest repelling, promoting photosynthesis, wind protection, insulation, etc., packaging materials such as bags for vegetables, fruits and gardening, pots and seedling boxes, soil materials, pumice, pipe materials, etc.). Among these, particularly in articles exposed to sunlight or other light, for example, automobile components, fans used outdoors (including outdoor units of air conditioners, agricultural circulation fans, etc.), filter members and honeycomb structure members used outdoors, gardening materials such as vinyl sheets for vinyl greenhouses, roofs and exterior walls of buildings, when the aqueous paint composition of the present embodiment is applied to an exposed surface exposed to sunlight or other light and a cured coating film is formed, the coating film is less likely to chalk and is highly durable, thereby providing a high ozone decomposition effect over a long period of time. Furthermore, as mentioned above, application of the aqueous coating composition of this embodiment to the desired application site is not limited to direct application, but may also be performed by applying the composition to a substrate such as a polyvinyl chloride sheet (wrapping sheet), drying to form a cured coating film on the sheet, and attaching the sheet with the cured coating film.

[0181] In particular, in the cured coating film of the aqueous paint composition of this embodiment, since one or more of acrylic resin, modified acrylic resin, and fluororesin are used as the binder, the cured coating film exhibits good chalking resistance and weather resistance even when the substrate is made of metal such as stainless steel (SUS) or aluminum, or of slate, concrete, wood, resin, etc.

[0182] In this way, in a coated article in which a cured coating film containing manganese oxide catalyst, activated carbon, acrylic resin, modified acrylic resin, or fluororesin, and one or more aqueous resins, and a dispersant, and containing water as the main component of the solvent, is formed on a substrate by applying the aqueous coating composition to the substrate and drying it, the ozone contained in the air is decomposed by contacting the cured coating film, and in particular, in a member constituting an air flow path, the ozone concentration can be effectively reduced, and the air can be effectively purified. In addition, if the aqueous coating composition contains manganese oxide catalyst, activated carbon, acrylic resin, modified acrylic resin, or fluororesin, and one or more aqueous resins, and a dispersant, and contains water as the main component of the solvent, the VOC emission is low and it is environmentally friendly.

[0183] As described above, the aqueous coating composition of the above embodiment is an aqueous coating composition containing a manganese oxide catalyst, activated carbon, an aqueous resin, and a dispersant, and having water as the main solvent component, and the aqueous resin is one or more of acrylic resin, modified acrylic resin, and fluororesin.

[0184] In addition, the cured coating film obtained by applying an aqueous coating composition containing a manganese oxide catalyst, activated carbon, one or more aqueous resins selected from acrylic resin, modified acrylic resin, and fluororesin, and a dispersant, and having water as the main component of the solvent, and then drying and curing, contains a manganese oxide catalyst, activated carbon, and one or more aqueous resins selected from acrylic resin, modified acrylic resin, and fluororesin. That is, the cured coating film in the above embodiment is a cured coating film containing a manganese oxide catalyst, activated carbon, and an aqueous resin, and the aqueous resin is one or more of acrylic resin, modified acrylic resin, and fluororesin.

[0185] In the cured coating film formed by applying and drying the aqueous coating composition of the above embodiment, one or more of acrylic resin, modified acrylic resin, and fluororesin are binder components, so that even if it contains a manganese oxide catalyst, it has high chalking resistance, i.e., weather resistance. Therefore, even under outdoor environmental conditions where it is exposed to sunlight or other light, the cured coating film applied to the substrate is not easily peeled off, making it possible to extend the life of the coating film and maintain high ozone decomposition for a long period of time.

[0186] In particular, in the above embodiment, if the acrylic resin or modified acrylic resin has a glass transition temperature (Tg) preferably within the range of -30°C to 130°C, the weather resistance can be improved and the heat resistance is also good. Furthermore, if the fluororesin has a glass transition temperature (Tg) within the range of -30°C to 100°C, the weather resistance can be improved and the heat resistance is also good.

[0187] In the above embodiment, the total amount of the manganese oxide catalyst and the activated carbon is preferably within a range of 25 to 75 parts by mass relative to 100 parts by mass of the total amount of the manganese oxide catalyst, the activated carbon, and the aqueous resin, so that both the ozone decomposition property and the weather resistance can be achieved, and more preferably within a range of 30 to 65 parts by mass.

[0188] In particular, the blending amount of one or more aqueous resins selected from acrylic resins, modified acrylic resins, and fluororesins, per 100 parts by mass of the total amount of the manganese oxide catalyst and activated carbon, is preferably within the range of 20 to 400 parts by mass, more preferably 25 to 350 parts by mass, even more preferably 30 to 300 parts by mass, and particularly preferably 50 to 280 parts by mass. Furthermore, when one or more aqueous resins selected from acrylic resins, modified acrylic resins, and fluororesins are blended in an amount of preferably 30 to 500 parts by mass relative to 100 parts by mass of the manganese oxide catalyst, ozone decomposability and weather resistance can be more effectively achieved, more preferably 40 to 480 parts by mass, even more preferably 45 to 450 parts by mass, and particularly preferably 70 to 400 parts by mass. In addition, if the manganese oxide catalyst is contained in an amount of preferably 5 to 65 parts by mass relative to 100 parts by mass of the total amount of the manganese oxide catalyst, the activated carbon, and the aqueous resin, it is possible to further achieve both ozone decomposition property and weather resistance, more preferably 10 to 60 parts by mass, even more preferably 15 to 55 parts by mass, and particularly preferably 18 to 50 parts by mass.

[0189] In addition, if the amount of the manganese oxide catalyst is within a range of preferably 11 to 900 parts by mass relative to 100 parts by mass of activated carbon, it is possible to achieve both coatability and weather resistance, more preferably within a range of 15 to 800 parts by mass, and even more preferably within a range of 20 to 700 parts by mass.

[0190] The above description can also be understood as an invention of a decomposition method for decomposing ozone in the atmosphere (air) by contacting a cured coating film containing a manganese oxide catalyst, activated carbon, and one or more aqueous resins selected from acrylic resin, modified acrylic resin, and fluororesin with the atmosphere (air). Alternatively, the invention can be considered as a method for forming a cured coating film, which comprises applying an aqueous coating composition according to the present embodiment, which contains a manganese oxide catalyst, activated carbon, a dispersant, at least one aqueous resin selected from modified acrylic resin and fluororesin, a pH adjuster, and water as a solvent, to an object to be coated, and then drying the composition. In this method for forming a cured coating film, since the aqueous coating composition uses water as the main solvent, it emits less VOCs and does not worsen the working environment when the coating composition is applied to a substrate and cured, i.e., when it is dried, making it environmentally friendly. Furthermore, the invention can also be regarded as a coated article (coated article, painted and coated article) in which a cured coating film containing a manganese oxide catalyst, activated carbon, and an aqueous resin is formed on a substrate surface, wherein the aqueous resin is one or more of acrylic resin, modified acrylic resin, and fluororesin.

[0191] In carrying out the present invention, the aqueous coating composition and its cured film, as well as the configuration, composition, blending, ingredients, shape, quantity, material, size, manufacturing method, etc. of other parts of the coated article to which it is applied are not limited to the present embodiment and examples. Furthermore, the numerical values ​​given in the present embodiment and examples do not indicate critical values ​​but indicate suitable values ​​suitable for carrying out the present invention, and therefore slight changes to the numerical values ​​do not negate the carrying out of the present invention.

Claims

1. An aqueous coating composition containing a manganese oxide catalyst, activated carbon, an aqueous resin as a binder, and a dispersant, and containing water as a main component of a solvent, The aqueous resin is a modified acrylic resin having a glass transition temperature (Tg) in the range of -30°C to 130°C or a fluororesin having a glass transition temperature (Tg) in the range of -30°C to 100°C.

2. 2. The aqueous coating composition according to claim 1, wherein the aqueous resin is blended in an amount within a range of 20 to 400 parts by mass per 100 parts by mass of the total amount of the manganese oxide catalyst and the activated carbon.

3. 3. The aqueous coating composition according to claim 1, wherein the aqueous resin is mixed in an amount within a range of 30 to 500 parts by mass per 100 parts by mass of the manganese oxide catalyst.

4. 4. The aqueous coating composition according to claim 1, wherein the total amount of the manganese oxide catalyst and the activated carbon is within a range of 25 parts by mass to 75 parts by mass per 100 parts by mass of the total amount of the manganese oxide catalyst, the activated carbon, and the aqueous resin.

5. 5. The aqueous coating composition according to claim 1, wherein the manganese oxide catalyst is mixed in an amount within the range of 11 to 900 parts by mass per 100 parts by mass of the activated carbon.

6. The aqueous coating composition according to any one of claims 1 to 5, characterized in that the manganese oxide catalyst is blended in an amount within the range of 5 parts by mass to 65 parts by mass per 100 parts by mass of the total amount of the manganese oxide catalyst, the activated carbon, and the aqueous resin.

7. A cured coating film comprising a manganese oxide catalyst, activated carbon, and an aqueous resin as a binder, The cured coating film is characterized in that the aqueous resin is a modified acrylic resin having a glass transition temperature (Tg) in the range of -30°C to 130°C or a fluororesin having a glass transition temperature (Tg) in the range of -30°C to 100°C.

8. The cured coating film according to claim 7, characterized in that the aqueous resin contains 20 parts by mass to 400 parts by mass per 100 parts by mass of the total amount of the manganese oxide catalyst and the activated carbon.

9. 9. The cured coating film according to claim 7, wherein the aqueous resin is contained in an amount within a range of 30 parts by mass to 500 parts by mass per 100 parts by mass of the manganese oxide catalyst.

10. The cured coating film according to any one of claims 7 to 9, characterized in that the total amount of the manganese oxide catalyst and the activated carbon is within a range of 25 parts by mass to 75 parts by mass per 100 parts by mass of the total amount of the manganese oxide catalyst, the activated carbon, and the aqueous resin.

11. The cured coating film according to any one of claims 7 to 10, characterized in that the manganese oxide catalyst is contained in an amount within a range of 11 parts by mass to 900 parts by mass per 100 parts by mass of the activated carbon.

12. The cured coating film according to any one of claims 7 to 11, characterized in that the manganese oxide catalyst is contained in an amount within a range of 5 parts by mass to 65 parts by mass per 100 parts by mass of the total amount of the manganese oxide catalyst, the activated carbon, and the aqueous resin.

13. A coated article having a cured coating film formed on a substrate surface, the cured coating film including a manganese oxide catalyst, activated carbon, and an aqueous resin as a binder, A coated article, wherein the aqueous resin is a modified acrylic resin having a glass transition temperature (Tg) in the range of -30°C to 130°C or a fluororesin having a glass transition temperature (Tg) in the range of -30°C to 100°C.

Citation Information

Patent Citations

  • Aqueous base coat composition

    CN111378335A

  • Water resin composition and anti-fouling paint

    CN1657576A

  • Aqueous (meth)acrylate copolymer dispersion, method for producing the same, and use thereof

    JP2003525324A

  • Surface treatment composition and surface-treated steel sheet

    JP2011111639A

  • Deodorizing catalyst unit, and manufacturing method therefor

    JP2015066478A